Method for producing recycled plastic and method for producing molded article of recycled plastic
A method for recycling plastic materials by integrating heating and melting steps without separating the base material and printed layer, using biomass-derived resins and additives, addresses efficiency and quality issues in plastic recycling, resulting in improved moldability and reduced extrusion-related defects.
Patent Information
- Application Number
- JP2023092191
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-05
- Publication Date
- 2024-12-17
AI Technical Summary
Existing methods for recycling plastic materials, particularly those containing polyolefin resins with printed layers, face challenges such as reduced production efficiency due to the need for a separation process between the base material and printed layer, leading to foreign matter and damage during extrusion.
A method for producing recycled plastic that integrates a heating and melting step without separating the base material and printed layer, using an extrusion device with specific conditions to minimize chlorine content and pressure, and incorporating biomass-derived resins and additives like antioxidants and compatibilizers to enhance compatibility and reduce foreign matter.
The method produces recycled plastic with improved moldability and reduced foreign matter and burns during extrusion, enhancing production efficiency and product quality.
Smart Images

Figure 2024174383000001 
Figure 2024174383000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing recycled plastics, which involves material recycling from printed matter or laminates containing polyolefin resins, and a method for producing molded articles from recycled plastics. [Background technology]
[0002] In recent years, plastic film packaging, plastic bottles, and other plastic products have been discarded and dumped as garbage in the ocean, causing environmental pollution problems. Plastic products are crushed in seawater and become submicron-sized fragments (microplastics), which float in the seawater. Microplastics are ingested by marine organisms such as fish and become concentrated in their bodies. As a result, there are concerns about the impact on the health of seabirds and humans who consume marine organisms as food.
[0003] In food packaging materials, polyolefin substrates such as polypropylene substrate (PP) and polyethylene substrate (PE) are often used as film substrates. Examples of food packaging materials include printed matter in which one side of a film substrate is printed with printing ink, and laminated laminates in which a film substrate is printed with printing ink and a sealant film is laminated on the printed layer, if necessary via an adhesive layer. The above-mentioned printed matter can reduce the amount of plastic because a sealant film is not required for lamination, but material recycling is difficult due to problems such as compatibility between the colorant and binder resin contained in the film substrate and the printed layer. On the other hand, laminated laminates have a demand for material recycling from the viewpoint of environmental load because a large amount of plastic is used as a film substrate.
[0004] As a material recycling method for packaging materials, an invention has been disclosed in which a printed matter and laminated packaging material with a removable printed layer on a plastic substrate is separated from the printed layer in a release liquid containing a surfactant (Patent Document 1). However, the presence of a printing layer release step increases the time required to complete processing and increases the amount of manual setup work, resulting in a problem of reduced production volume. Note that the invention described in Patent Document 1 does not at all anticipate a method for material recycling packaging materials without separating the printed layer. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2021 / 230032 Summary of the Invention [Problem to be solved by the invention]
[0006] An object of the present invention is to provide a method for producing recycled plastics which have excellent moldability and which produce little foreign matter and little discoloration immediately after the start of extrusion and after continuous extrusion. [Means for solving the problem]
[0007] As a result of extensive research, the inventors have found that the above problems can be solved by using the method for producing recycled plastic described below, and have thus completed the present invention.
[0008] That is, the present invention relates to the following [1] to
[16] .
[0009] [1] A method for producing recycled plastic, comprising the steps of: obtaining recycled plastic (B) from a printed matter or laminate (A) using an extrusion device equipped with a first screw and a discharge section; The printed matter and the laminate (A) have not undergone a process of removing the substrate and the printed layer, The printed matter or laminate (A) comprises a substrate and a printed layer, and The printed matter or laminate (A) contains 80 mass% or more of polyolefin resin, The chlorine content of the printed matter or laminated product (A) is 0.4 mass% or less based on the total mass of the printed matter or laminated product (A), The printed matter or laminate (A) contains a biomass-derived resin, The biomass-derived resin is At least one resin selected from the group consisting of a urethane resin, a rosin resin, and a cellulose resin, a heating, melting and kneading step of heating, melting and kneading the printed matter or laminate (A) in the extrusion device to obtain a resin composition (a); and A method for producing recycled plastic, comprising an extrusion step in which the resin composition (a) is extruded from a discharge portion of an extrusion device at a pressure of 18 MPa or less.
[0010] [2] The method for producing recycled plastic according to [1], wherein the heating and melting temperature is 120 to 280°C.
[0011] [3] A method for producing recycled plastics according to [1] or [2], wherein the biomass content of the printed matter or laminate (A) is 0.5% or more.
[0012] [4] A method for producing recycled plastics according to any one of [1] to [3], wherein the urethane resin contains structural units derived from polyester, which is a condensation product of a dibasic acid and a diol, and the dibasic acid contains at least one selected from the group consisting of sebacic acid, succinic acid, and dimer acid.
[0013] [5] The method for producing recycled plastics according to any one of [1] to [4], wherein the printed matter or laminate (A) further contains a polyvinyl acetal resin.
[0014] [6] The method for producing recycled plastics according to any one of [1] to [5], wherein the polyolefin resin comprises a polyethylene resin and / or a polypropylene resin.
[0015] [7] The method for producing recycled plastics according to any one of [1] to [6], wherein the printed matter or laminate (A) further comprises a barrier layer.
[0016] [8] The method for producing recycled plastics described in [7], wherein the barrier layer is at least one selected from the group consisting of a vapor deposition layer including a vapor deposition film, a barrier coat layer, and a barrier adhesive layer.
[0017] [9] The method for producing recycled plastics described in any one of [1] to [8], further comprising a water cooling step.
[0018]
[10] The method for producing recycled plastics according to any one of [1] to [9], wherein the printed matter or laminate (A) has a melt mass flow rate of 0.5 to 15 g / 10 min.
[0019]
[11] The method for producing recycled plastics according to any one of [1] to
[10] , wherein the printed layer contains a binder resin, and the chlorine content of the binder resin is 5 mass% or less.
[0020]
[12] The method for producing recycled plastics according to any one of [1] to
[11] , wherein the rotation speed of the first screw of the extrusion device is 50 to 1000 rpm.
[0021]
[13] The method for producing recycled plastics according to any one of [1] to
[12] , wherein the printed matter or laminate (A) further comprises an adhesive layer, and the adhesive layer comprises a cured product of a polyisocyanate and a polyol.
[0022]
[14] The method for producing recycled plastics according to any one of [1] to
[13] , wherein the heating, melting and kneading step is carried out in the presence of an antioxidant.
[0023]
[15] The method for producing recycled plastics according to any one of [1] to
[14] , wherein the heating, melting and kneading step is carried out in the presence of a compatibilizer.
[0024]
[16] A method for producing a molded product made of recycled plastic, the molded product being produced by the method for producing recycled plastic described in any one of [1] to
[15] . Effect of the Invention
[0025] According to the present invention, it is possible to provide a method for producing recycled plastics which has excellent moldability and produces little foreign matter and little discoloration immediately after the start of extrusion and after continuous extrusion. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0026] The following describes in detail the embodiments of the present invention. However, the embodiments or explanations of the requirements described are merely examples of the embodiments of the present invention, and the present invention is not limited to these contents as long as they do not depart from the gist of the present invention.
[0027] In this specification, the printed matter or laminate (A) may be abbreviated simply as "printed matter or laminate (A)", but these terms have the same meaning.
[0028] (Manufacturing method of recycled plastics) The present invention is a method for producing recycled plastics, in which a recycled plastic (B) is obtained from a printed matter or laminated laminate (A) using an extrusion device equipped with a first screw and a discharge section, wherein the printed matter or laminated laminate (A) has not been subjected to a process of removing a substrate and a printed layer, the printed matter or laminated laminate (A) includes a substrate layer and a printed layer, the chlorine content is 0.4 mass% or less based on the total mass of the printed matter or laminated laminate (A), and the printed matter or laminated laminate (A) contains a polyolefin resin in an amount of 80 mass% or more based on the total mass of the printed matter or laminated laminate (A), and the printed matter or laminated laminate (A) includes a biomass-derived resin, a heating and melting kneading step in which the biomass-derived resin contains at least one selected from the group consisting of a urethane resin, a rosin resin, and a cellulose resin, and the printed matter or laminate (A) is heated, melted, and kneaded in the extrusion device to obtain a resin composition (a); and The method is characterized in that it includes an extrusion step in which the resin composition (a) is extruded from a discharge portion of an extrusion device at a pressure of 18 MPa or less.
[0029] The detachment process in the phrase "the printed matter has not undergone a detachment process in which the substrate and the printed layer are detached" refers to a detachment and removal process in which most of the printed layer is detached and removed from the printed matter, for example, using an alkali, and if the printed layer is unintentionally removed for some reason, it cannot be said to have "undergone a detachment process."
[0030] In the manufacturing method of the present invention, the printed matter or laminated laminate (A) is heated, melted, and kneaded, whereby (1) the molten base layer suppresses aggregation of the colorant that may be contained in the printed layer and is compatible with the biomass resin contained in the printed layer, thereby improving the compatibility between the components of the printed matter or laminated laminate (A) during the heating, melting, and kneading process, and (2) the chlorine content of the printed matter or laminated laminate (A) is 0.4 mass% or less based on the total mass of the printed matter or laminated laminate (A), thereby improving the compatibility between the components of the printed matter or laminated laminate (A) during the heating, melting, and kneading process. It is possible to suppress foaming of recycled plastics and damage to equipment due to the generation of chlorine gas, (3) the content of polyolefin resin (A) in the printed matter or laminated laminate (A) is 80 mass% or more based on the total mass% of the printed matter or laminated laminate (A), so that the base layer and the printed layer are kneaded without layer separation in the heat melt kneading process, and (4) the pressure of the discharge part of the extrusion device is set to 18 MPa or less, so that foreign matter is prevented from passing through the filter, and it is thought that the generation of foreign matter and discoloration immediately after the start of extrusion and after continuous extrusion can be suppressed. Note that the mechanism of the above-mentioned effect is merely a guess and does not limit the invention in any way.
[0031] The foreign matter and discoloration immediately after the start of extrusion, which is the subject of the present invention, refers to the foreign matter and discoloration of the recycled plastic that is initially discharged from the discharge part of the extrusion device after the printed material is fed into the extrusion device in the heating, melting and kneading process. Also, the foreign matter and discoloration after continuous extrusion refers to the foreign matter and discoloration of the recycled plastic that is discharged from the discharge part of the extrusion device after the production of recycled plastic has been continued for 5 hours in the extrusion device. The above-mentioned foreign matter and discoloration were evaluated visually by heating and melting the recycled plastic again and forming it into a film.
[0032] The manufacturing method of the present invention essentially includes a heating, melting and kneading step of heating, melting and kneading the printed matter to obtain a resin composition (a) and an extrusion step of extruding the obtained resin composition (a), but preferably further includes a cooling step of cooling the extruded resin composition (a) to obtain a recycled plastic. The shape of the obtained recycled plastic is not particularly limited, and examples thereof include a rod-like, granular, cubic, rectangular, and amorphous shape.
[0033] From the viewpoint of the handling of the printed matter or laminated laminate (A), the manufacturing method of the present invention preferably includes a crushing step of crushing the packaging material before the heating and melting kneading step. From the viewpoint of removing foreign matter such as dust and dirt, it is preferable to include a cleaning step of washing the printed matter or laminated laminate (A) before the heating and melting kneading step. From the viewpoint of removing moisture, it is preferable to include a dehydration and drying step of dehydrating and drying the printed matter or laminated laminate (A) before the heating and melting kneading step. In addition, it is preferable to carry out the heating and melting kneading step in the presence of additives such as antioxidants and compatibilizers. From the viewpoint of removing foreign matter, it is preferable that the extrusion device is equipped with a foreign matter separator at its discharge section. From the viewpoint of the handling of the recycled plastic, it is preferable to include a pelletizing step of shredding the extruded resin composition after or simultaneously with the cooling step. In addition, it is preferable to carry out the heating and melting kneading step in the presence of additives such as antioxidants and compatibilizers.
[0034] <Crushing process> The crushing step is preferably carried out before the heating melt kneading step. The crushing step is preferably carried out before or simultaneously with the washing step described below, and more preferably before the washing step described below. The crushing method is not particularly limited, and examples thereof include a method using a jaw crusher, an impact crusher, a cutter mill, a stamp mill, a ring mill, a roller mill, a jet mill, or a hammer mill. The size of the fragments of the printed matter or laminated laminate (A) after crushing is preferably 1 mm to 50 mm in side length, more preferably 3 mm to 40 mm, even more preferably 5 mm to 30 mm, and particularly preferably 8 mm to 20 mm. When the size of the fragments of the printed matter or laminated laminate (A) after crushing is within the above range, the efficiency of the washing step and the dehydration and drying step due to the expansion of the surface area and the homogenization of the resin composition are promoted, and the generation of foreign matter immediately after the start of extrusion and after continuous extrusion can be suppressed.
[0035] <Cleaning process> The washing step is preferably carried out on the printed matter or laminated laminate (A) before the heating, melting and kneading step, and is preferably carried out on the crushed printed matter or laminated laminate (A) after the above-mentioned crushing step. Examples of the washing method include a batch method and a continuous method, and a washing liquid such as water, a detergent, a neutralizing agent, an aqueous alkaline solution, etc. may be used.
[0036] <Dehydration drying process> The dehydration and drying step is preferably carried out on the printed matter or laminated laminate (A) before the heating, melting and kneading step, and the dehydration method is preferably a centrifugal dehydration method, and the drying method is preferably a hot air drying method. In the dehydration and drying step, either dehydration or drying alone may be carried out, but it is preferable to carry out both dehydration and drying. The moisture content in the printed matter or laminated laminate (A) after the dehydration and drying step is preferably 3% by mass or less, more preferably 2% by mass or less, even more preferably 1% by mass or less, and particularly preferably 0.6% by mass or less, based on the total mass of the printed matter or laminated laminate (A). When the moisture content in the printed matter or laminated laminate (A) after the dehydration and drying step is within the above range, foaming due to evaporation of water during heating and melting can be suppressed.
[0037] <Heat melt kneading process> The heating, melting and kneading step is a step of heating, melting and kneading the printed matter or laminated laminate (A) using an extrusion device equipped with a first screw, and in this step, the printed matter or laminated laminate (A) is heated and melted, and further kneaded by the first screw, so that the individual printed matter or laminated laminate (A) is transformed into a continuous phase resin composition. The higher the uniformity of the resin composition, the more the generation of foreign matter can be suppressed immediately after the start of extrusion of the recycled plastic and after continuous extrusion. In the heating, melting and kneading step, it is preferable to add an antioxidant for the purpose of suppressing the occurrence of scorching of the recycled plastic caused by the resin composition.
[0038] In the heat-melting and kneading step, the heat-melting temperature is preferably 120°C to 280°C, more preferably 170°C to 250°C, and even more preferably 180°C to 240°C. When the heat-melting temperature is within the above range, the recycled plastic can have both uniformity and low thermal history, so that the generation of foreign matter immediately after the start of extrusion and after continuous extrusion can be suppressed. The above heat-melting temperature range needs to be determined taking into consideration the glass transition temperature and melting temperature of the printed matter or laminate (A), the shape of the recycled plastic, and the pressure applied in the molding step.
[0039] The rotation speed of the first screw is preferably 50 to 1000 rpm, more preferably 80 rpm to 850 rpm, and even more preferably 100 rpm to 600 rpm. When the rotation speed of the first screw is within the above range, the balance between the uniformity of the recycled plastic, the short residence time in the extrusion device, and the suppression of shear heat generation is good, so that foreign matter and scorching can be suppressed immediately after the start of extrusion and after continuous extrusion. The screw rotation speed of 50 to 900 rpm corresponds to a shear rate of 222 to 4004 sec-1. The shear rate was calculated using the following formula under the conditions of the examples described later. Formula: (pi) x (screw diameter) x (screw rotation speed) / {(60 x (minimum gap distance between the cylinder inner wall and the screw)} Screw diameter: 34mm Minimum clearance between the cylinder inner wall and the screw: 0.4mm
[0040] During long runs, if the extrusion device is equipped with a foreign matter separator described later, the foreign matter separator may collect foreign matter, causing a pressure rise due to partial blockage and a temperature rise in the extrusion device due to accumulation of shear heat. However, by setting the screw rotation speed to 50 rpm or more, the residence time of the resin composition in the extrusion device is not significantly increased even after partial blockage, and the occurrence of scorching can be suppressed. On the other hand, by setting the screw rotation speed to 1000 rpm or less, the reincorporation of the collected foreign matter can be suppressed, and further, thermal decomposition due to shear heat can be suppressed, thereby suppressing the generation of foreign matter.
[0041] The residence time of the resin composition in the extrusion device is preferably 10 to 120 seconds, more preferably 15 to 80 seconds, and particularly preferably 20 to 40 seconds. When the residence time of the resin composition is within the above range, the heating time and kneading efficiency are good, so that the generation of foreign matter immediately after the start of extrusion and after continuous extrusion can be suppressed.
[0042] (Extrusion Equipment) The extrusion device used in the manufacturing method of the present invention is equipped with a first screw and a discharge part. The extrusion device is a device that can melt and mold a commonly used thermoplastic resin, and for example, a known extrusion device described in JP 2017-148997 A can be used. Specifically, the extrusion device preferably has a first supply port for supplying material, a heating and melting kneading section for heating, melting and kneading the material such as a thermoplastic resin supplied from the first supply port, and a discharge section for discharging the thermoplastic resin heated, melted and kneaded in the heating and melting kneading section.
[0043] In the extrusion device, the material is melted by shear heat caused by the rotation of the first screw and heating by an electric heater, etc., and the molten material is kneaded by the rotation of the first screw. Examples of the extrusion device include a twin-screw extruder, a single-screw extruder, and a rotor-type twin-screw kneader, but from the viewpoint of kneading efficiency, a twin-screw extruder or a rotor-type twin-screw kneader is preferred.
[0044] <How to add additives> In the manufacturing method of the present invention, the heating and melting kneading step is preferably carried out in the presence of an antioxidant and / or a compatibilizer. The antioxidant and / or the compatibilizer are different from those previously contained in the printed matter or the laminated laminate (A). In addition, known additives other than the antioxidant and the compatibilizer may be added within a range that does not impair the effects of the present invention. As a method for adding the additive, a method in which the printed matter to which the additive has been added is supplied from the first supply port in the heating and melting kneading step, or a method in which the additive is added using an extrusion device equipped with a second supply port and a second screw are preferred examples. The extrusion device can be produced by connecting barrels, so that one or more of the barrels can be equipped with a second supply port and a second screw, and the positions of the second supply port and the second screw may be anywhere in the extrusion device. It is preferable that the additive added from the second supply port is mixed into the resin composition that has been introduced and heated and melted from the first supply port while being kneaded by the second screw.
[0045] (Additives) Examples of the additives include antioxidants, compatibilizers, lubricants, weather stabilizers, plasticizers, and antistatic agents, and it is preferable to include an antioxidant and a compatibilizer.
[0046] (Antioxidants) By using an antioxidant, the occurrence of scorching can be suppressed, and recycled plastics with less scorching immediately after the start of extrusion and after continuous extrusion can be obtained. As the antioxidant, known antioxidants such as phenol-based, phosphoric acid-based, sulfur-based, and amine-based antioxidants can be used, but phenol-based and phosphoric acid-based antioxidants are preferred. The additive rate of the antioxidant is preferably 0.01 to 3 mass% based on the total mass of the printed matter and / or plastic laminate, more preferably 0.05 to 2 mass%, even more preferably 0.05 to 2 mass%, and particularly preferably 0.1 to 0.5 mass%. When the additive rate of the antioxidant is within the above range, the occurrence of scorching immediately after the start of extrusion and after continuous extrusion can be suppressed.
[0047] (Phenol-based antioxidant) Examples of the phenol-based antioxidant include monophenol-based, bisphenol-based, trisphenol-based, tetraphenol-based, polyphenol-based, and thiobisphenol-based antioxidants. The bisphenol-based, trisphenol-based, and tetraphenol-based antioxidants, which have a large anti-burning effect, are preferred, and the tetraphenol-based antioxidants are more preferred.
[0048] As commercially available phenolic antioxidants, Irganox 1010, Irganox 1076, Irganox 245 (manufactured by BASF), etc. can be used.
[0049] (Phosphate-based antioxidant) Examples of the phosphoric acid-based antioxidant include monononyl-based, dinonyl-based, trinonyl-based, allyl-based, alkylaryl-based, monoalkyl-based, dialkyl-based, trialkyl-based, and dioxa-based antioxidants. Of these, the trinonyl-based, allyl-based, alkylaryl-based, trialkyl-based, and dioxa-based antioxidants are preferred, as they have a greater tanning suppression effect, and the dioxa-based antioxidants are more preferred.
[0050] Commercially available phosphoric acid-based antioxidants that can be used include Irgafos168 (manufactured by BASF) and ADK STAB PEP-36 (manufactured by ADEKA).
[0051] (Compatibilizer) By using a compatibilizer, the colorant and binder resin derived from the printed layer can be more easily mixed with other components, making it possible to obtain recycled plastic with less foreign matter immediately after the start of extrusion and after continuous extrusion. The compatibilizer preferably contains a polyolefin copolymer, and suitable examples of the polyolefin copolymer include polyolefin-styrene copolymer, polyolefin-acrylic copolymer, polyolefin-acrylonitrile copolymer, (maleic anhydride) modified polyolefin, etc. However, the polyolefin copolymer is not limited to these. The "copolymer" may be a block copolymer, a random copolymer, or a graft copolymer. (Hereinafter, in the case of a graft copolymer, it will be expressed as main chain = g = side chain.) Preferred forms of the compatibilizer include polyethylene=g=polystyrene, polyethylene=g=styrene-acrylonitrile copolymer, polypropylene=g=styrene-acrylonitrile copolymer, ethylene-ethyl acrylate copolymer=g=styrene-acrylonitrile copolymer, oxazoline group-containing polystyrene, polycarbonate=g=glycidyl methacrylate-styrene-acrylonitrile copolymer, maleic anhydride-modified polyolefin, and the like, with maleic anhydride-modified polyolefin being preferred.
[0052] Examples of maleic anhydride-modified polyolefins include maleic anhydride-modified polyethylene, maleic anhydride-modified polypropylene, maleic anhydride-modified ethylene-butene copolymer, ethylene-glycidyl methacrylate copolymer, and maleic anhydride-modified styrene-butadiene copolymer, and among these, maleic anhydride-modified polyethylene and maleic anhydride-modified polypropylene are preferred.
[0053] The addition rate of the compatibilizer is preferably 0.01 to 1 mass %, more preferably 0.05 to 0.8 mass %, further preferably 0.05 to 0.5 mass %, and particularly preferably 0.1 to 0.2 mass %, based on the total mass of the printed matter and / or laminate. When the addition rate of the compatibilizer is within the above range, the compatibility between the binder resin derived from the printed layer and / or laminate and the polyolefin resin is improved, so that the generation of foreign matter immediately after the start of extrusion and after continuous extrusion can be suppressed.
[0054] As the compatibilizer, commercially available products such as Admer Q series (manufactured by Mitsui Chemicals, Inc.) and Eumex series (manufactured by Sanyo Chemical Industries, Ltd.) can be used.
[0055] (lubricant) The lubricant serves to reduce friction between the resin compositions in the extrusion device and between the resin composition and the extrusion device. Examples of the lubricant include hydrocarbon-based lubricants such as paraffin wax and synthetic polyethylene, fatty acid-based lubricants such as stearic acid and behenin, higher alcohol-based lubricants such as stearyl alcohol, fatty acid amide-based lubricants such as stearic acid amide, oleic acid amide, and erucic acid amide, metal soap-based lubricants such as calcium, zinc, and magnesium stearate, and ester-based lubricants such as glycerin monostearate and glycerin monooleate, with fatty acid amide-based lubricants being preferred.
[0056] The addition rate of the lubricant is preferably 0.01 to 5 mass %, more preferably 0.03 to 3 mass %, and even more preferably 0.05 to 1 mass %, based on the total mass of the printed matter and / or plastic laminate.
[0057] As the lubricant, commercially available products such as Fatty Acid Amide S (manufactured by Kao Corporation) and Fatty Acid Amide ON can be used.
[0058] (Weather resistance stabilizer) Weathering stabilizers absorb ultraviolet rays and extend the weathering life of plastics. Examples of weathering stabilizers include benzotriazoles, triazines, benzophenones, benzoates, and hindered amines.
[0059] The addition rate of the weather resistance stabilizer is preferably 0.05 to 5 mass %, and more preferably 0.1 to 2 mass %, based on the total mass of the printed matter and / or plastic laminate.
[0060] As the weather resistance stabilizer, commercially available products such as Adeka STAB ALA series (manufactured by ADEKA CORPORATION) can be used.
[0061] (Plasticizer) Plasticizers have the role of imparting flexibility to plastics. Examples of plasticizers include epoxidized vegetable oils such as epoxidized soybean oil and epoxidized linseed oil, phthalate esters such as dioctyl phthalate and dibutyl phthalate, and polyesters such as polyesters of dibasic acids and glycols.
[0062] The addition rate of the plasticizer is preferably 0.1 to 50 mass %, more preferably 0.5 to 30 mass %, and even more preferably 1 to 15 mass %, based on the total mass of the printed matter and / or plastic laminate.
[0063] As the plasticizer, commercially available products such as Adesizer PN series (manufactured by ADEKA Corporation) can be used.
[0064] (Antistatic agent) Antistatic agents have the role of preventing plastics from becoming electrostatically charged. Examples of antistatic agents include fatty acid sulfonates and fatty acid esters.
[0065] As the antistatic agent, commercially available products such as Electromaster series (manufactured by Kao Corporation) and Electrostripper (manufactured by Kao Corporation) can be used.
[0066] The addition rate of the antistatic agent is preferably 0.05 to 3 mass %, and more preferably 0.1 to 2 mass %, based on the total mass of the printed matter and / or plastic laminate.
[0067] <Extrusion process> In the extrusion step, the resin composition is discharged from a discharge part of the extrusion device. In one embodiment, it is preferable that the discharge part includes a foreign matter separator, and the resin composition is discharged after passing through the foreign matter separator. In discharging the heated, melted and kneaded resin composition, the extrusion pressure of the extruder is 18 MPa or less, preferably 0.1 to 18 MPa, more preferably 1 to 12 MPa, and even more preferably 3 to 7 MPa, from the viewpoint of durability of the extruder. The extrusion pressure of the extruder does not need to be constant all the time, but the extrusion pressure referred to here is the maximum extrusion pressure during the extrusion process. When the extrusion pressure is within the above range, the foreign matter separation efficiency by the foreign matter separator is good, so that the generation of foreign matter immediately after the start of extrusion and after continuous extrusion can be suppressed. The discharge pressure is affected by the processing temperature, screw rotation speed, discharge amount, resin viscosity, and the foreign matter separator (screen mesh, etc.) used to remove foreign matter from the recycled plastic. In addition, clogging of the mesh by insoluble matter, foreign matter, etc., and foaming due to moisture, chlorine-containing substances, etc. are also factors that cause pressure changes.
[0068] The discharge rate of the extrusion device is preferably 5 to 60 kg per hour, more preferably 10 to 50 kg, and particularly preferably 15 to 40 kg per hour. When it is within the above range, the discharge pressure and kneading efficiency are good, so that the generation of foreign matter and scorching can be suppressed immediately after the start of extrusion of the recycled plastic and after continuous extrusion.
[0069] (Foreign matter separation device) The discharge section of the extrusion device is preferably equipped with a foreign matter separation device to remove foreign matter in the resin composition. Examples of the foreign matter separation device include a screen mesh (metal mesh). Examples of the screen mesh include woven types such as plain weave, twill weave, plain tatami weave, and twill tatami weave, and punched metal types, but from the viewpoint of removing foreign matter, plain weave is preferred. Taking into consideration the removal of foreign matter, the discharge pressure, and clogging, the size of the screen mesh is preferably 20 to 200 mesh, more preferably 60 to 150 mesh, and further preferably 80 to 140 mesh.
[0070] <Cooling process> The resin composition extruded in the extrusion step is preferably cooled in the cooling step to form a recycled plastic. Examples of the cooling method in the cooling step include air cooling, wind cooling, and water cooling. In the present invention, it is preferable to include a water cooling step. The cooling temperature in the cooling step is preferably 20°C to 80°C, and more preferably 30°C to 60°C. The cooling step may be carried out simultaneously with the pelletizing step described below, or may be carried out after the pelletizing step. Specifically, for example, the extruded resin composition (D) may be pelletized while being air-cooled immediately after extrusion, and then water-cooled.
[0071] <Pelletizing process> The recycled plastic may be processed into pellets by a pelletizing process, or may be pelletized during the cooling process. Examples of the pelletizing method include a hot cut method and a strand cut method, and are not particularly limited. However, in consideration of continuous productivity, the hot cut method is preferred.
[0072] (Printed matter or laminate (A)) In the method for producing recycled plastics of the present invention, a printed matter or laminate (A) is used as a raw material. The printed matter or laminate (A) includes a substrate layer and a printed layer. Specifically, the configuration can be exemplified as follows, but is not limited to these. In the following configuration notation, " / " means the boundary between each layer. The adhesive layer is not limited to the adhesive used in the conventionally known methods of dry lamination and non-sol lamination, but also includes cases where it is made of polyolefin resin or other thermoplastic resin in extrusion lamination. In addition, when each layer such as a printed layer is actually laminated in contact with multiple layers, such as the first printed layer and the second printed layer, they are simply referred to as a printed layer. (1) Substrate / printing layer / adhesive layer / sealant (2) Substrate / printed layer / adhesive layer / intermediate substrate / adhesive layer / sealant (3) Substrate / printed layer / adhesive layer / first intermediate substrate / adhesive layer / second intermediate substrate / adhesive layer / sealant (4) Base material / Print layer / Thermoplastic resin layer (5) Substrate / printed layer / (AC agent layer) / thermoplastic resin layer / sealant (6) Substrate / printed layer / (AC agent layer) / thermoplastic resin layer / intermediate substrate / (AC agent layer) / thermoplastic resin layer / sealant (7) Substrate / printed layer / adhesive layer / intermediate substrate / (AC agent layer) / thermoplastic resin layer / sealant (8) Substrate / printed layer / (AC agent layer) / thermoplastic resin layer / intermediate substrate / adhesive layer / sealant (9) Printing layer / base material (10) Printing layer / substrate / heat sealant layer (11) Printing layer / sealant (12) Printing layer / substrate / adhesive layer / sealant (13) Printing layer / substrate / adhesive layer / intermediate substrate / adhesive layer / sealant (14) Printing layer / substrate / (AC agent layer) / thermoplastic resin layer / sealant
[0073] In the above configurations, the AC agent layer refers to an anchor coating agent layer, and () indicates an optional configuration. Each of the above configurations may also preferably further include a barrier layer, and the preferred form of the barrier layer is at least one selected from a deposition layer, a barrier coating layer, and a barrier adhesive layer.
[0074] A preferred embodiment including a barrier layer is shown below. (15) Substrate / deposition layer / printed layer / adhesive layer / sealant (16) Substrate / printed layer / adhesive layer / vapor deposition layer / intermediate substrate / adhesive / sealant (17) Substrate / printed layer / adhesive layer / vapor deposition layer / sealant (18) Substrate / barrier coat layer / printing layer / adhesive layer / sealant (19) Substrate / printing layer / barrier coat layer / adhesive layer / sealant (20) Substrate / printing layer / barrier adhesive layer / sealant However, the present invention is not limited to these forms.
[0075] (Biomass-derived resin) The printed matter or laminated laminate (A) contains a biomass-derived resin, and the biomass-derived resin contains at least one selected from the group consisting of urethane resin, rosin resin, and cellulose resin. The biomass degree of the printed matter or laminated laminate (A) is preferably 1% or more, more preferably 3% or more, even more preferably 5% or more, and particularly preferably 10%. The higher the biomass degree, the more the amount of fossil fuel-derived components used can be reduced, and the more the environmental load can be reduced. Here, the "biomass degree" indicates the mass ratio of the biomass-derived components.
[0076] The biomass-derived resin may be contained in any layer of the printed matter or laminated product (A), but is preferably contained in the printed layer as a binder resin, and when the printed matter or laminated product (A) has an adhesive layer, it is also preferably contained in the adhesive layer.
[0077] (Polyolefin resin) Since the present invention is mainly focused on the production of recycled polyolefin resin, the printed matter used contains polyolefin resin in an amount of 80% by mass or more based on the total mass of the printed matter. The polyolefin resin content is more preferably 85% by mass or more, even more preferably 90% by mass or more, and even more preferably 95% by mass or more. When it is within the above range, the homogeneity of the resin composition is improved, so that the generation of foreign matter immediately after the start of extrusion of the recycled plastic and after continuous extrusion can be suppressed. The polyolefin is preferably polypropylene and / or polyethylene. The polypropylene is more preferably a copolymer with ethylene and / or butene.
[0078] (Embodiments of printed matter or laminate (A)) When the printed matter or laminate (A) has a substrate and a sealant, it is more preferable that it has the following form. (1) Both the base material and the sealant contain polypropylene In this case, the heat melting temperature of the laminate (A) is preferably from 150 to 250°C, more preferably from 180 to 230°C, and further preferably from 190 to 220°C. (2) The base material includes polypropylene and the sealant includes polyethylene. In this case, the heat melting temperature of the laminate (A) is preferably from 140 to 240°C, more preferably from 170 to 220°C, and further preferably from 180 to 210°C. (3) Both the base material and the sealant contain polyethylene In this case, the heat melting temperature of the laminate (A) is preferably from 130 to 230°C, more preferably from 160 to 210°C, and further preferably from 170 to 200°C.
[0079] (Chlorine content) Due to halogen elements that may be contained in the printed matter or laminate (A), halogen gas or hydrogen chloride, an acidic gas, may be generated during the production of recycled plastics, which may damage equipment or pose a risk to human health. Furthermore, if bubbles are generated during the production of recycled plastics, the surface of the molded product may be easily uneven when the recycled plastic is used to produce the molded product, which may deteriorate the surface condition of the molded product. Therefore, the chlorine content of the printed matter or laminate (A) must be 0.4 mass% or less, preferably 0.2 mass% or less, and more preferably 0.1 mass% or less, based on the total mass of the printed matter or laminate (A).
[0080] (Method for measuring chlorine content in printed matter or laminate (A)) In the present invention, the chlorine content of the printed matter or laminate (A) is measured in accordance with JIS K0127 (2013). In this measurement method, a sample pretreated by a combustion method is quantified by ion chromatography.
[0081] (Melt mass flow rate (MFR) of printed matter or laminate (A)) The melt mass flow rate (MFR) of the printed matter or laminate (A) is measured by crushing it into pieces with a side length of 5 mm to 10 mm. The MFR in the present invention is a value measured in accordance with JIS K7210 at a temperature of 190° C. and a pressure of 2.6 kgf. The MFR of the printed matter or laminate (A) is preferably from 0.5 to 15 g / 10 min, more preferably from 1.0 to 14 g / 10 min, and further preferably from 3 to 13 g / 10 min. When the MFR of the printed matter or laminate (A) is within the above range, the fluidity in the heating, melting and kneading step is improved, so that the occurrence of burns immediately after the start of extrusion and after continuous extrusion can be suppressed.
[0082] (base material) The substrate is preferably a plastic substrate mainly containing polyolefin resin as a raw material. The substrate is preferably in the form of a film or sheet, since the uniformity of the recycled plastic is improved, resulting in a reduction in foreign matter and an improvement in tensile strength. Substrates primarily containing polyolefin resins have higher heat resistance than ester-based substrates, and are less susceptible to thermal decomposition or hydrolysis during the heating, melting and kneading process and the recycled plastic molding process, allowing the molecular weight to be maintained high. Further, suitable examples of plastic substrates mainly containing polyolefin resins include biaxially oriented polypropylene (OPP), non-oriented polypropylene (CPP), polyethylene such as low density polyethylene (LDPE), linear low density polyethylene (LLDPE), medium density polyethylene (MDPE), high density polyethylene (HDPE), acid-modified polyethylene, acid-modified polypropylene, copolymer polypropylene, and films laminated with these. The thickness of the substrate is not particularly limited, and is preferably 5 μm or more and 150 μm or less, more preferably 10 μm or more and 70 μm or less, from the viewpoint of reducing foreign matter and improving the tensile strength of recycled plastics. In addition, films having heat sealability are preferably used, and CPP, heat sealable OPP, etc. are suitable.
[0083] The substrate mainly containing polyolefin resin (C) may be a simple laminate of polyolefin substrates, or a substrate different from the polyolefin substrate may be laminated. The "substrate different from the polyolefin substrate" may be a film having properties different from the polyolefin substrate, and may be of any type. In addition, in the case of a laminated substrate, it may be in a form including an adhesive layer. The method of laminating plastics is not particularly limited, and may be a conventionally known method such as coextrusion, heat fusion, and pressure bonding via an adhesive layer.
[0084] The substrate is preferably in a form containing additives such as antistatic agents, antifogging agents, and ultraviolet protection agents by coating or kneading, in a form having an easily adhesive coating layer (e.g., a layer containing polyvinyl alcohol and its derivatives), in a form in which the surface of the substrate is corona-treated or low-temperature plasma-treated, in a form in which the substrate is a barrier substrate having a vapor deposition layer or a barrier coating layer, etc. The above-mentioned additions and processing are also carried out for the purpose of improving the wettability of printing inks and other coating agents, or for the purpose of imparting specific functionality to the film, and are suitably used, for example, to provide a packaging material with excellent visibility of the contents by preventing fogging of the packaging material due to moisture.
[0085] (Printing layer) The printed layer can be a layer that displays any design, pattern, letter, symbol, etc. for the purpose of providing decoration or aesthetics; displaying the contents, expiration date, and manufacturer or seller. The printed layer may be a solid printed layer that does not have a design, pattern, letter, symbol, etc. The method for forming the printed layer is not particularly limited, and it can be formed, for example, using a printing ink containing a colorant and a binder resin. The printed layer may be a single layer or a multi-layer structure, and may be provided on the surface layer. The thickness of the printed layer is 0.1 to 12 g / m 2 It is preferable that the thickness is 0.5 to 6 g / m 2 More preferably, it is 1 to 3 g / m 2 It is more preferable that:
[0086] (binder resin) As described above, the printed layer of the printed matter or laminate (A) preferably contains a binder resin and is preferably formed using a printing ink containing a binder resin. In the present invention, the binder resin contains a biomass-derived resin, and the biomass-derived resin contains at least one resin selected from the group consisting of a urethane resin, a rosin resin, and a cellulose resin.
[0087] (urethane resin) In the present invention, the urethane resin preferably contains a structural unit derived from polyester, which is a condensate of a dibasic acid and a diol, and the dibasic acid and / or diol are preferably biomass-derived components. The dibasic acid preferably contains at least one selected from the group consisting of sebacic acid, succinic acid, and dimer acid. By containing these dibasic acids, hydrolysis becomes easier in the above-mentioned washing step and the like, and high-quality recycled plastic can be obtained. The dibasic acid more preferably contains sebacic acid and / or succinic acid, and particularly preferably contains sebacic acid.
[0088] The method for producing the urethane resin is not particularly limited, and the urethane resin is produced by a known method. The urethane resin is preferably a urethane resin made of a polyol and a polyisocyanate, or a urethane resin obtained by reacting a urethane prepolymer having a terminal isocyanate made of a polyol and a polyisocyanate with a polyamine. For example, the method described in JP-A-2013-256551 can be used as the production method. In order to obtain a structural unit derived from a polyester which is a condensation product of a dibasic acid and a diol, it is preferable to use a polyester polyol which is a condensation product of a dibasic acid and a diol as the polyol.
[0089] (Polyisocyanate) The polyisocyanate preferably contains a diisocyanate. Examples of the diisocyanate include aliphatic diisocyanates such as tetramethylene diisocyanate, isopropylene diisocyanate, methylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, and 2,4,4-trimethylhexamethylene diisocyanate; cyclohexane-1,4-diisocyanate, hydrogenated xylylene diisocyanate, isophorone diisocyanate, lysine diisocyanate, dicyclohexylmethane-4,4'-diisocyanate, 1,3-bis(isocyanatomethyl)cyclohexane, methylcyclohexane diisocyanate, m-tetramethylxylylene diisocyanate, and dimers in which the carboxyl groups of dimer acids are converted to isocyanate groups. alicyclic diisocyanates such as α,α,α,α'-tetramethylxylylene diisocyanate, 1,5-naphthylene diisocyanate, 4,4'-diphenylmethane diisocyanate, 4,4'-diphenyldimethylmethane diisocyanate, 4,4'-dibenzyl isocyanate, dimethyldiphenylmethane diisocyanate, tetramethyldiphenylmethane diisocyanate, 1,3-phenylene diisocyanate, 1,4-phenylene diisocyanate, m-xylylene diisocyanate, p-xylylene diisocyanate, o-xylylene diisocyanate, and aromatic diisocyanates such as 2,4-tolylene diisocyanate and 2,6-tolylene diisocyanate. Among these, from the viewpoints of easy reaction control and good balance of the performance of the resulting urethane resin, alicyclic or araliphatic diisocyanates are preferred, and isophorone diisocyanate and α,α,α,α'-tetramethylxylylene diisocyanate are particularly preferred. At least one diisocyanate may be used, and two or more diisocyanates may be used in combination.
[0090] In the present invention, it is also preferable to use an isocyanate derived from biomass as the polyisocyanate. For example, a diisocyanate derived from biomass can be obtained by converting a dicarboxylic acid derived from biomass into a terminal amino group by acid amidation and reduction, and then reacting it with phosgene to convert the amino group into an isocyanate group. The use of an isocyanate derived from biomass can contribute to reducing the environmental load.
[0091] Examples of biomass-derived isocyanates include dimer acid diisocyanate (DDI), octamethylene diisocyanate, and decamethylene diisocyanate. Also, plant-derived isocyanate compounds can be obtained by using biomass-derived amino acids as raw materials and converting their amino groups to isocyanate groups. For example, lysine diisocyanate (LDI) can be obtained by methyl esterifying the carboxyl groups of lysine and then converting the amino groups to isocyanate groups. Also, 1,5-pentamethylene diisocyanate can be obtained by decarboxylating the carboxyl groups of lysine and then converting the amino groups to isocyanate groups. Also, polymers or oligomers obtained by polymerizing the above-mentioned isocyanate compounds and diol compounds so that the terminals are isocyanate groups can be used.
[0092] (Polyol) The polyol preferably contains a structural unit derived from a polyester which is a condensation product of a dibasic acid and a diol, the dibasic acid and / or the diol are preferably biomass-derived components, and the dibasic acid preferably contains at least one selected from the group consisting of sebacic acid, succinic acid, and dimer acid. In order to incorporate a structural unit derived from a polyester which is a condensation product of a dibasic acid and a diol into the polyol, it is preferable to use a polyester polyol which is a condensation product of a dibasic acid and a diol. In addition to the polyester polyol, it is also possible to use a polyester polyol which does not contain the dibasic acid, a polyether polyol, a polycarbonate polyol, or a polyolefin polyol in combination.
[0093] The number average molecular weight of the polyol is preferably 500 to 10,000. Here, the number average molecular weight of the polyol is calculated from the hydroxyl value, which is a value calculated by esterifying or acetylating the hydroxyl groups in the resin, back titrating the remaining acid with an alkali, converting the amount of hydroxyl groups in 1 g of the resin into mg of potassium hydroxide, and is a value measured according to JIS K0070. When the number average molecular weight of the polyol is 10,000 or less, the ink has excellent blocking resistance to the plastic substrate. Also, when the number average molecular weight of the polyol is 500 or more, the flexibility of the urethane resin film is excellent, and the ink has excellent adhesion to the plastic film. For the above reasons, the number average molecular weight of the polyol is more preferably 1,000 to 5,000.
[0094] The polyol is preferably a diol. The diol refers to a compound having two hydroxyl groups in one molecule. Examples of the diol include polyester polyol, polyether diol, polycarbonate, polybutadiene glycol, and other polyols. At least one diol may be used, and two or more diols may be used in combination.
[0095] Suitable examples of diols used in the polyester polyol include ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, 1,3-propanediol, 1,4-butanediol, 1,3-butanediol, 1,6-hexanediol, 1,8-octanediol, 1,9-nonanediol, neopentyl glycol, 3-methyl-1,5-pentanediol, 2-methyl-1,3-propanediol, 3,3,5-trimethylpentanediol, 2,4-diethyl-1,5-pentanediol, 1,12-octadecanediol, 1,2-alkanediol, 1,3-alkanediol, 1-monoglyceride, 2-monoglyceride, 1-monoglycerin ether, 2-monoglycerin ether, dimer diol, and hydrogenated dimer diol. As for the diol, it is preferable to use a combination of a linear diol such as ethylene glycol, 1,4-butanediol, or 1,3-propanediol and a branched diol such as propylene glycol, neopentyl glycol, or 3-methyl-1,5-pentanediol.
[0096] Suitable biomass-derived diols include 1,3-propanediol, 1,4-butanediol, and ethylene glycol.
[0097] The dibasic acid used in the polyester polyol is preferably a biomass-derived component, and more preferably contains at least one selected from the group consisting of sebacic acid, succinic acid, and dimer acid. Other dibasic acids include adipic acid, phthalic anhydride, isophthalic acid, terephthalic acid, maleic acid, fumaric acid, oxalic acid, malonic acid, pimelic acid, azelaic acid, suberic acid, glutaric acid, 1,4-cyclohexyl dibasic acid, and hydrogenated dimer acid. In the total mass of the dibasic acid, it is preferable to contain at least one selected from the group consisting of sebacic acid, succinic acid, and dimer acid in an amount of 5% by mass or more, more preferably 10% by mass, and even more preferably 20% by mass. Among them, it is preferable that the dibasic acid contains at least sebacic acid.
[0098] Furthermore, a polyol having three or more hydroxyl groups and / or a polyvalent carboxylic acid having three or more carboxyl groups can be used in combination as a raw material for the polyester polyol.
[0099] (Chain extender) The chain extender is preferably a polyamine. Suitable examples of the polyamine include, but are not limited to, ethylenediamine, propylenediamine, hexamethylenediamine, isophoronediamine, dicyclohexylmethane-4,4'-diamine, and diamines obtained by converting the carboxyl groups of dimer acid to amino groups. These may be used alone or in combination of two or more.
[0100] Amino acids can also be used as chain extenders. The term "amino acid" refers to a compound having both an amino group and an acidic functional group in one molecule, and preferred examples include glutamine, asparagine, lysine, diaminopropionic acid, ornithine, diaminobenzoic acid, and diaminobenzenesulfonic acid. In addition, in the synthesis process of the urethane resin, the acidic group is highly likely to remain unreacted with the isocyanate group, so that the acidic group remains in the urethane resin and the acid value can be maintained.
[0101] (Reaction stopper) In the case of a urethane resin that can be produced only by the urethanization step, it is preferable to use a monoalcohol or a monoamine as the reaction terminator, and in the case of a urethane resin that is produced by carrying out a urethanization reaction step in addition to the urethanization step, it is preferable to use a monoamine. The monoalcohol is preferably a substituted or unsubstituted alcohol, and suitable examples thereof include methanol, ethanol, n-propanol, isopropyl alcohol, and 1-butanol. The monoamine is preferably a substituted or unsubstituted monoamine, and suitable examples thereof include n-butylamine, n-dibutylamine, octylamine, diethylamine, monoethanolamine, monopropanolamine, diethanolamine, dipropanolamine, etc. As the reaction terminator, the compounds exemplified as the chain extender can also be used, and at least one of them may be used, or two or more of them may be used in combination.
[0102] In producing a urethane prepolymer having an isocyanate group at its end obtained by reacting a polyisocyanate with a polyol, the molar equivalent ratio of NCO of the polyisocyanate to OH of the polyol (molar equivalent of NCO of the polyisocyanate / molar equivalent of OH of the polyol compound) is preferably 1.3 to 3, more preferably 1.5 to 2.
[0103] The urethane resin preferably has an active hydrogen group such as a hydroxyl group and / or an amino group. This is to obtain a reaction site with the isocyanate-based curing agent described later. When the urethane resin has a hydroxyl group, the hydroxyl value is preferably 0.5 to 30 mgKOH / g, more preferably 1 to 20 mgKOH / g, and even more preferably 2 to 15 mgKOH / g. When the urethane resin has an amino group, the amine value is preferably 0.1 to 15 mgKOH / g, and even more preferably 1 to 12 mgKOH / g. On the other hand, the acid value of the urethane resin is preferably 5 mgKOH / g or less, and even more preferably 3 mgKOH / g or less. This is because the acid group is difficult to react with the isocyanate-based curing agent described later.
[0104] The mass average molecular weight of the urethane resin is preferably from 5,000 to 100,000, more preferably from 7,000 to 90,000, and further preferably from 10,000 to 80,000. The mass average molecular weight of the present invention can be measured by gel permeation chromatography (GPC). For example, Water2690 (manufactured by Waters Corporation) or HLC-8220 (manufactured by Tosoh Corporation) can be used as a GPC device, and PLgel, 5 μm, MIXED-D (manufactured by Polymer Laboratories) or TSKgel Super AW series (manufactured by Tosoh Corporation) can be used as a column. The mass average molecular weight can be determined as a polystyrene equivalent value.
[0105] (rosin resin) Rosin resin refers to a substance having a structural unit derived from rosin acid (e.g., abietic acid, neoabietic acid, palustric acid, pimaric acid, isopimaric acid, dehydroabietic acid) as the main component. Here, having a certain structural unit as the main component means that the structural unit accounts for 50 mass% or more. The rosin acid or rosin resin may be hydrogenated. The rosin resin is preferably at least one selected from the group consisting of rosin-modified phenolic resins, rosin ester resins, rosin-modified maleic acid resins, and polymerized rosin resins. The acid value of the rosin resin is preferably 350 mgKOH / g or less, more preferably 250 mgKOH / g or less, and further preferably 150 mgKOH / g or less. In one embodiment, the acid value is preferably 100 mgKOH / g or less, more preferably 50 mgKOH / g or less. The softening point of the rosin resin is preferably 60 to 180° C., and more preferably 70 to 150° C. In this specification, the softening point is a value measured by the ring and ball method, and can be measured in accordance with JIS K2207.
[0106] (rosin ester) The rosin resin is preferably a rosin ester, which is an ester condensation resin of a low molecular weight polyol having a molecular weight of 1,000 or less and a rosin acid. The number of hydroxyl groups is 2 to 4 (hereinafter, sometimes abbreviated as difunctional to tetrafunctional) and the molecular weight is 50 to 500. As such a low molecular weight polyol, for example, difunctional low molecular weight polyols such as ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,10-decanediol, etc.; trifunctional low molecular weight polyols such as glycerin, trimethylolpropane, etc.; tetrafunctional low molecular weight polyols such as erythritol, pentaerythritol, etc. are preferably used. Among them, trifunctional and / or tetrafunctional low molecular weight polyols are preferred. The mass average molecular weight of the rosin ester is preferably 500 to 2,000, and more preferably 500 to 1,500.
[0107] (Cellulose resin) Examples of the cellulose resin include nitrocellulose, cellulose acetate propionate, cellulose acetate butyrate, hydroxyalkyl cellulose, and carboxyalkyl cellulose. The alkyl group may be, for example, a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, a pentyl group, or a hexyl group. The alkyl group may further have a substituent. Among these, cellulose acetate propionate, cellulose acetate butyrate, and nitrocellulose are preferred. The mass average molecular weight of the cellulose resin is preferably 5,000 to 200,000, more preferably 10,000 to 10,000, and even more preferably 15,000 to 80,000. The glass transition point of the cellulose resin is preferably 120°C to 180°C, and more preferably 130 to 170°C. By using the above-mentioned urethane resin in combination with the cellulose resin, printability, blocking resistance, and the like are improved.
[0108] (nitrocellulose) Nitrocellulose is preferably obtained as a nitric acid ester by reacting natural cellulose with nitric acid to replace three hydroxyl groups in a six-membered ring of an anhydrous glucopyranose group in the natural cellulose with nitric acid groups, and has an average degree of polymerization of 35 to 480, more preferably 50 to 200. When the average degree of polymerization is 50 or more, the strength of the ink film is improved, and the abrasion resistance and rubbing resistance are improved, which is preferable. Also, when the average degree of polymerization is 200 or less, the solubility in solvents, the low-temperature stability of the ink, and the compatibility with the co-used resin are improved, which is preferable. Also, the nitrogen content is preferably 10.5 to 12.5% by mass.
[0109] (Cellulose Acetate Alkynate) Cellulose acetate alkylate is obtained by reacting cellulose with an appropriate organic acid and an acid anhydride. That is, cellulose is mixed with an appropriate organic acid, an acid anhydride, and a catalyst, and reacted until a triester is formed. After complete triesterization, it is hydrolyzed to obtain the desired hydroxyl group level. Cellulose acetate is obtained by triesterization with acetic acid and then hydrolysis. Generally, resins with an acetylation degree of 0.6-2.5% by mass and a hydroxyl group ratio of 1.8-5.0% are commercially available. Cellulose acetate propionate is obtained by triesterization with acetic acid and propionic acid and then hydrolysis. Generally, resins with an acetylation degree of 0.6-2.5% by mass, a propionation degree of 42.0-46.0% by mass, and a hydroxyl group ratio of 1.8-5.0% are commercially available. Cellulose acetate butyrate is obtained by triesterization with acetic acid and butyric acid and then hydrolysis. Generally, resins with an acetylation degree of 2.0 to 30.0% by mass, a butyrylation degree of 17.0 to 53.0% by mass, and a hydroxyl group ratio of 1.0 to 5.0% are commercially available. The above cellulose-based resins can be used alone or in combination of two or more. In the present invention, it is preferable to use cellulose acetate propionate or cellulose acetate butyrate.
[0110] In the present invention, the printed layer of the printed matter or laminate (A) preferably contains a biomass-derived resin as a binder resin, and preferably contains at least one selected from the group consisting of urethane resin, rosin resin, and cellulose resin, but it is also possible to use other resins as binder resins in combination. Resins that can be used in combination are not limited to the following, but include polyamide resins, ethylene-vinyl acetate copolymer resins, vinyl chloride-vinyl acetate copolymer resins, vinyl acetate resins, acrylic resins, styrene resins, dammar resins, styrene-maleic acid copolymer resins, polyester resins, alkyd resins, terpene resins, phenol-modified terpene resins, ketone resins, cyclized rubbers, butyral, polyacetal resins, polyvinyl acetal resins, petroleum resins, and modified resins thereof. These resins can be used in a mixture of two or more. Among the above, it is preferable to include a combination of a urethane resin and a cellulose resin, and / or a combination of a cellulose resin and a polyamide resin.
[0111] (Polyvinyl acetal resin) The polyvinyl acetal resin is an acetal cyclized product of reacting polyvinyl alcohol with an aldehyde such as butyraldehyde and / or formaldehyde, and preferably contains vinyl alcohol units, vinyl acetate units, and an acetal ring group. The polyvinyl acetal resin preferably contains 60 to 90 mass% of acetal rings, 5 to 30 mass% of vinyl alcohol units, and 0.5 to 10 mass% of vinyl acetate units, and is more preferably a polyvinyl butyral resin having a butyral ring as the acetal ring. The mass average molecular weight of the polyvinyl acetal resin is preferably 10,000 to 100,000, and more preferably 10,000 to 80,000.The glass transition point of the polyvinyl acetal resin is preferably 50 to 80°C, and more preferably 60 to 75°C.
[0112] When a plurality of resins are used in combination as the binder resin, it is preferable to use in combination a resin having a glass transition temperature of -60°C or more and less than 40°C and a resin having a glass transition temperature of 40°C or more and 200°C or less. It is more preferable to use in combination a resin having a glass transition temperature of -50°C to 0°C and a resin having a glass transition temperature of 50°C to 190°C. In the present invention, the glass transition temperature is a value measured by a differential scanning calorimeter (DSC).
[0113] (Chlorine content of binder resin in print layer) The chlorine content of the binder resin contained in the print layer is preferably 5% by mass or less, and may be 0. Here, the chlorine content is the content (% by mass) of chlorine atoms based on the mass of the binder resin. If the chlorine content of the binder resin is 5% by mass or less, the binder resin is excellent in environmental safety and is less likely to generate free chlorine. The chlorine content is more preferably 4% by mass or less, further preferably 3% by mass or less, and particularly preferably 2% by mass or less.
[0114] In the present invention, the chlorine content of the resin is measured in accordance with JIS K0127 (2013). In this measurement method, a sample pretreated by a combustion method is quantified by ion chromatography. The chlorine content of the printed layer can be simply calculated from the chlorine content of each of the raw materials constituting the printed layer using the following formula: The same applies to each of the other layers. Formula: Chlorine content (%) in total mass of binder resin solids = mass of chlorine in total mass of binder resin solids / total mass of binder resin solids (%) Formula: Chlorine content (%) in total mass of solids in printed layer = mass of chlorine in total mass of solids in printed layer / total mass of solids in printed layer (%)
[0115] (Coloring agent) The printed layer preferably contains a colorant. The colorant is preferably a pigment, and either an organic pigment or an inorganic pigment can be used. The colorant may be used alone or in combination of two or more types. In consideration of quality deterioration due to coloring of recycled plastics, the content of the colorant in the total mass of the printed layer is preferably 30% by mass or less, more preferably 25% by mass or less, and even more preferably 23% by mass or less. The colorant is preferably a pigment, and either an organic pigment, an inorganic pigment, or an extender pigment can be used. However, inorganic pigments containing titanium oxide are preferred, and extender pigments such as silica, barium sulfate, kaolin, clay, calcium carbonate, and magnesium carbonate are preferred. Organic pigments are preferably made of organic compounds or organometallic complexes.
[0116] (Organic pigments) Examples of the organic pigment include, but are not limited to, soluble azo pigments, insoluble azo pigments, azo pigments, phthalocyanine pigments, halogenated phthalocyanine pigments, anthraquinone pigments, anthanthrone pigments, dianthraquinonyl pigments, anthrapyrimidine pigments, perylene pigments, perinone pigments, quinacridone pigments, thioindigo pigments, dioxazine pigments, isoindolinone pigments, quinophthalone pigments, azomethine azo pigments, flavanthrone pigments, diketopyrrolopyrrole pigments, isoindoline pigments, indanthrone pigments, and carbon black pigments. Further examples include carmine 6B, lake red C, permanent red 2B, disazo yellow, pyrazolone orange, carmine FB, chromophthalic yellow, chromophthalic red, phthalocyanine blue, phthalocyanine green, dioxazine violet, quinacridone magenta, quinacridone red, indanthrone blue, pyrimidine yellow, thioindigo bordeaux, thioindigo magenta, perylene red, perinone orange, isoindolinone yellow, aniline black, diketopyrrolopyrrole red, and daylight fluorescent pigments.
[0117] The hue of the organic pigment is preferably at least one selected from the group consisting of black pigments, cyan pigments, green pigments, red pigments, purple pigments, yellow pigments, orange pigments, and brown pigments. Furthermore, at least one or more selected from the group consisting of black pigments, cyan pigments, red pigments, and yellow pigments are preferable. Specific examples of organic pigments are shown by CI numbers in the Color Index International (abbreviated as CI). Preferable are CI Pigment Red 57:1, CI Pigment Red 48:1, CI Pigment Red 48:2, CI Pigment Red 48:3, CI Pigment Red 146, CI Pigment Red 242, CI Pigment Yellow 83, CI Pigment Yellow 14, CI Pigment Orange 38, CI Pigment Orange 13, CI Pigment Yellow 180, CI Pigment Yellow 139, CI Pigment Red 185, CI Pigment Red 122, and CI Pigment Red 178. , CI Pigment Red 149, CI Pigment Red 144, CI Pigment Red 166, CI Pigment Violet 23, CI Pigment Violet 37, CI Pigment Blue 15, CI Pigment Blue 15:1, CI Pigment Blue 15:2, CI Pigment Blue 15:3, CI Pigment Blue 15:4, CI Pigment Blue 15:6, CI Pigment Green 7, CI Pigment Orange 34, CI Pigment Orange 64, CI Pigment Black 7.
[0118] Examples of inorganic pigments include titanium oxide, zinc oxide, zinc sulfide, barium sulfate, calcium carbonate, chromium oxide, silica, aluminum particles, mica, bronze powder, chrome vermilion, yellow lead, cadmium yellow, cadmium red, ultramarine, Prussian blue, red iron oxide, yellow iron oxide, iron black, titanium oxide, and zinc oxide. Aluminum can be either leafing or non-leafing type, with the non-leafing type being preferred.
[0119] (Formation of printing layer) The printing layer can be formed, for example, by printing on a substrate using a printing ink and then removing the volatile components. The printing method is preferably a gravure printing method or a flexographic printing method, and, for example, the ink is diluted with a diluting solvent to a viscosity and concentration suitable for gravure printing, and is supplied to each printing unit alone or in a mixture and applied. The printing layer can then be obtained by fixing the coating by drying in an oven or the like.
[0120] (Printing ink manufacturing method) The printing ink used to form the printing layer can be produced, for example, by dispersing a pigment in an organic solvent with a resin or the like using a dispersing machine, and then mixing the resulting pigment dispersion with a resin, various additives, an organic solvent, and the like. As the dispersing machine, a commonly used machine, for example, a roller mill, a ball mill, a pebble mill, an attritor, or a sand mill, can be used. The particle size distribution of the pigment in the pigment dispersion can be adjusted by appropriately adjusting the size of the grinding media of the dispersing machine, the packing rate of the grinding media, the dispersion processing time, the discharge speed of the pigment dispersion, the viscosity of the pigment dispersion, and the like. The viscosity of the printing ink at 25°C is preferably in the range of 10 to 1000 mPa·s or less from the viewpoint of preventing the pigment from settling and dispersing appropriately. The above viscosity is measured at 25°C using a Tokimec Co., Ltd. B-type viscometer.
[0121] [Barrier layer] The printed matter or laminate (A) may further include a barrier layer. The barrier layer exists for the purpose of imparting barrier properties to the printed matter, and the barrier layer exists to control the permeation of objects to be barriered, such as light, magnetism, and various gases, through the packaging material, and contains a barrier component. The barrier layer is preferably one or more types selected from the group consisting of a vapor deposition layer, a barrier coat layer, and a barrier adhesive layer.
[0122] (deposited layer) When the printed matter or laminate (A) has a vapor-deposited layer as a barrier layer, the vapor-deposited layer preferably includes a vapor-deposited film, and it is preferable to use, as the vapor-deposited layer, one or more selected from the group consisting of a substrate having a vapor-deposited film, an intermediate substrate having a vapor-deposited film, and a sealant having a vapor-deposited film. By having a vapor deposition layer including a vapor deposition film, the printed matter or laminate (A) has high gas barrier properties, specifically oxygen barrier properties and water vapor barrier properties, and in addition, a packaging container made using the printed matter or laminate (A) can suppress the loss in mass of the contents filled therein.
[0123] The vapor-deposited film may be a vapor-deposited film of one or more inorganic substances or inorganic oxides such as silicon (Si), aluminum (Al), magnesium (Mg), calcium (Ca), potassium (K), tin (Sn), sodium (Na), boron (B), titanium (Ti), lead (Pb), zirconium (Zr), yttrium (Y), etc. The vapor-deposited film may be composed of two or more layers, and may be composed of the same material or different materials. Among the above, from the viewpoints of adhesion and gas barrier properties, the vapor-deposited film is preferably made of aluminum, aluminum oxide (alumina) or silicon oxide (silica).
[0124] The thickness of the evaporated film is preferably 1 nm or more and 150 nm or less, more preferably 5 nm or more and 60 nm or less, and even more preferably 10 nm or more and 40 nm or less. By making the thickness of the vapor-deposited film 1 nm or more, the oxygen barrier property and water vapor barrier property of the vapor-deposited layer can be further improved. Furthermore, by making the thickness of the vapor-deposited film 150 nm or less, it is possible to suppress the generation of foreign matter immediately after the start of extrusion of the recycled plastic and after continuous extrusion.
[0125] The method for forming the vapor-deposited film may be a conventional method, for example, a physical vapor deposition method (PVD method) such as a vacuum deposition method, a sputtering method, or an ion plating method, or a chemical vapor deposition method (CVD method) such as a plasma chemical vapor deposition method, a thermal chemical vapor deposition method, or a photochemical vapor deposition method.
[0126] (Barrier coat layer) When the printed matter or laminate (A) has a barrier coat layer as a barrier layer, the barrier coat layer is formed by a barrier coating agent. The barrier coat layer is preferably adjacent to the substrate, intermediate substrate, sealant and / or printed layer. This can improve the oxygen barrier property and water vapor barrier property.
[0127] The barrier coating agent may be, for example, a coating agent made of a resin alone, including gas barrier resins such as vinyl chloride-vinylidene chloride copolymer, vinyl acetate-vinylidene chloride copolymer, acrylate-vinylidene chloride copolymer, ethylene-vinyl alcohol copolymer (EVOH), polyvinyl alcohol, polyacrylonitrile, polyamide resin, polyester resin, polyurethane resin, or (meth)acrylic resin, or a coating agent made of an inorganic layered compound and a resin, as described below. The inorganic layered compound is, for example, a clay mineral such as a kaolinite group, a smectite group, or a mica group, and is a crystalline inorganic compound having a layered structure. The type, particle size, aspect ratio, etc. of these inorganic layered compounds are appropriately selected and are not particularly limited. Among them, the smectite group such as montmorillonite, hectorite, and saponite are suitable, and resin is easily incorporated between the layers of the inorganic layered compound to form a composite. In particular, among this group, montmorillonite has the best stability in a molten state and coatability.
[0128] The resin used in the barrier coating agent consisting of the inorganic layered compound and the resin is not particularly limited as long as it is easily incorporated between the layers of the inorganic layered compound, but it is preferable to use a water-soluble polymer. Examples of the water-soluble polymer include polyvinyl alcohol (PVA), polyvinylpyrrolidone, starch, methyl cellulose, carboxymethyl cellulose, acrylic resin, and sodium alginate. In particular, when polyvinyl alcohol (PVA) is used as the coating agent for the gas barrier laminate of the present invention, the gas barrier property is most excellent.
[0129] The barrier coat layer may further comprise a composition containing a hydrolysis / polycondensation product of a metal alkoxide. The metal alkoxide is a compound represented by the following general formula, M(OR)n, where M is a metal, R is an alkyl group, and n is the coordination number of the alkoxy group. It is preferable that M is selected from the group consisting of Si, Ti, Ar, and Zr, and R is selected from a methyl group and an ethyl group. In particular, it is preferable to use tetraethoxysilane [Si(OC2H5)4], triisopropoxyaluminum [Al(O-2'-C3H7)3], or the like, because the hydrolysis product of the alkoxide is relatively stable in an aqueous solvent.
[0130] The above-mentioned components can be added to the coating agent alone or in combination. Furthermore, known additives such as an isocyanate compound, a silane coupling agent, a dispersant, a stabilizer, a viscosity adjuster, a colorant, etc. can be added within a range that does not impair the barrier properties of the coating agent.
[0131] The barrier coat layer can be formed by dissolving or dispersing the above-mentioned material in water or a suitable solvent, applying the solution, and drying the solution. Alternatively, the barrier coat layer can be formed by applying a commercially available barrier coat agent and drying the solution.
[0132] The barrier coating agent can be applied by any of the commonly used conventional methods such as dipping, roll coating, screen printing, spraying, etc.
[0133] The thickness of the barrier coat layer is preferably from 0.01 μm to 10 μm, more preferably from 0.1 μm to 5 μm, and further preferably from 0.3 μm to 3 μm. By making the thickness of the barrier coat layer 0.01 μm or more, the oxygen barrier property and water vapor barrier property of the printed matter or laminate (A) can be improved. By making the thickness of the barrier coat layer 10 μm or less, the amount of foreign matter immediately after the start of extrusion of the recycled plastic and after continuous extrusion can be reduced, and further, the tensile strength is excellent.
[0134] (Barrier adhesive layer) The printed matter or laminate (A) may have a barrier adhesive layer as a barrier layer. The barrier adhesive layer can be formed, for example, by applying and drying a commercially available barrier adhesive. As the barrier adhesive, for example, gas barrier adhesives such as TM-9310 (manufactured by Toyo-Morton), Maxive (manufactured by Mitsubishi Gas Corporation), and PASLIM (manufactured by DIC Corporation) are preferably used. The thickness of the barrier adhesive layer is preferably 0.1 to 10 μm, more preferably 0.5 to 5 μm, and particularly preferably 1.0 to 2.5 μm.
[0135] (Adhesive layers other than the barrier adhesive layer) The printed matter or laminate (A) may have an adhesive layer other than the barrier adhesive layer. The method of providing an adhesive layer to bond (also referred to as laminating) each layer is not particularly limited, and examples thereof include conventionally known methods such as extrusion lamination, dry lamination, and non-solvent lamination.
[0136] The components constituting the adhesive layer are not particularly limited as long as they can adhere each layer, and suitable examples include olefin-based adhesives, acrylic-based adhesives, ethylene-vinyl acetate copolymer-based adhesives, reactive urethane adhesives (including dry adhesives and non-solvent adhesives), imine-based anchor coating agents, other anchor coating agents, thermoplastic resins used in extrusion lamination, and the like. The adhesive layer preferably contains a cured product of a reactive urethane adhesive containing polyisocyanate and polyol. The adhesive layer preferably contains a bio-derived resin.
[0137] The reactive urethane adhesive is preferably a two-liquid type urethane adhesive consisting of a polyol as a main agent and a polyisocyanate as a curing agent. The polyol may be any compound having two or more hydroxyl groups, and may be selected from known polyols. Examples of polyols include polyester polyols, polycarbonate polyols, polycaprolactone polyols, polyether polyols, polyolefin polyols, acrylic polyols, silicone polyols, castor oil polyols, hydrogenated castor oil polyols, dimer diols, hydrogenated dimer diols, and fluorine-based polyols. Among them, polyester polyols, polyether polyols, castor oil polyols, and hydrogenated castor oil polyols are more preferred, and polyester polyols and castor oil polyols are even more preferred. The polyester polyol is preferably, for example, one that contains a structural unit derived from a polyester, which is a condensate of a dibasic acid and a diol, and the dibasic acid contains at least one selected from the group consisting of sebacic acid, succinic acid, and dimer acid.
[0138] The polyol may be an acid-modified product in which a part of the hydroxyl groups in the polyol is modified with an acid, or a product in which a part of the hydroxyl groups in the polyol is reacted with a diisocyanate to introduce a urethane bond. The polyisocyanate may be a compound having two or more isocyanate groups, and may be selected from known polyisocyanates. Examples of the polyisocyanate include aromatic polyisocyanates, araliphatic polyisocyanates, aliphatic polyisocyanates, alicyclic polyisocyanates, and modified products thereof. The polyol may be used alone or in combination of two or more kinds. The same applies to the polyisocyanate. In addition, the above-mentioned biomass-derived isocyanates and / or biomass-derived diols can be used as the polyisocyanate and / or polyol.
[0139] (Intermediate substrate layer) The printed matter or laminate (A) may further have an intermediate substrate layer. A specific example of the intermediate substrate layer is preferably a plastic substrate mainly containing polyolefin resin as a raw material, similar to the substrate layer. Examples of the intermediate substrate layer include polyolefin resins such as low density polyethylene (LDPE), linear low density polyethylene (LLDPE), medium density polyethylene (MDPE), high density polyethylene (HDPE), ethylene-vinyl acetate copolymer, propylene homopolymer, and ethylene-propylene copolymer. A composite substrate produced by a co-extrusion method may also be used.
[0140] (Sealant) The printed matter or laminate (A) may further have a sealant. The inner layer side of the sealant comes into direct contact with the packaged item, and plays a role in protecting the packaged item. In order to make the printed matter or laminate (A) into a bag shape, it is preferable that the innermost layer of the sealant has heat sealability. Examples of materials constituting the sealant include polyolefin resins such as low density polyethylene (LDPE), linear low density polyethylene (LLDPE), medium density polyethylene (MDPE), high density polyethylene (HDPE), ethylene-vinyl acetate copolymer, propylene homopolymer, and ethylene-propylene copolymer, and one or more of these resins can be used. The sealant may be composed of a single layer or may be composed of two or more layers. In order to suppress shrinkage during heat sealing, the sealant is preferably a non-stretched film made of the above-mentioned resin. The sealant may be a milky white base material kneaded with pigments or the like, or a composite base material produced by a co-extrusion method.
[0141] The thickness of the sealant is not particularly limited and is appropriately set depending on the use of the printed matter or laminate (A) and the type and properties of the packaged item, but is usually preferably 10 to 200 μm. In the case of a pouch (particularly a retort pouch), the thickness of the sealant is preferably 20 to 150 μm, more preferably 25 to 130 μm.
[0142] (Recycled plastic) Using the above-mentioned method for producing recycled plastic, recycled plastic can be obtained from the printed matter or laminate (A). The recycled plastic may contain pigments and binder resins derived from the printed layer. It may also contain additives added in the heat-melt-kneading process.
[0143] (Pigment content in recycled plastics) The content of the pigment in the recycled plastic is preferably 5% by mass or less, more preferably 3% by mass or less, and even more preferably 1.5% by mass or less, based on 100% by mass of the recycled plastic. When the content of the pigment in the recycled plastic is within the above range, the generation of foreign matter immediately after the start of extrusion of the recycled plastic and after continuous extrusion can be suppressed.
[0144] (Binder resin content in recycled plastics) The content of the binder resin in the recycled plastic is preferably 10% by mass or less, more preferably 7% by mass or less, and particularly preferably 5% by mass or less, based on 100% by mass of the recycled plastic. When the content of the binder resin in the recycled plastic is within the above range, the generation of foreign matter immediately after the start of extrusion of the recycled plastic and after continuous extrusion can be suppressed.
[0145] (Antioxidant content in recycled plastics) The content of the antioxidant in the recycled plastic is preferably 0.01 to 5 mass%, more preferably 0.01 to 3 mass%, further preferably 0.05 to 1 mass%, and particularly preferably 0.1 to 0.5 mass%, based on 100 mass% of the recycled plastic. When the content of the antioxidant in the recycled plastic is within the above range, the occurrence of scorching immediately after the start of extrusion of the recycled plastic and after continuous extrusion can be suppressed.
[0146] (Compatibilizer content in recycled plastics) The content of the compatibilizer in the recycled plastic is preferably 0.01 to 3 mass%, and more preferably 0.05 to 0.5 mass%, based on 100 mass% of the recycled plastic. When the content of the compatibilizer in the recycled plastic is within the above range, the occurrence of burns immediately after the start of extrusion of the recycled plastic and after continuous extrusion can be suppressed.
[0147] <Melt mass flow rate (MFR) of recycled plastics> The melt mass flow rate (MFR) of the recycled plastic is greatly affected by the thermal history such as the temperature during molding and the cooling speed. The melt mass flow rate (MFR) of the recycled plastic is preferably 0.5 to 20 g / 10 min, more preferably 3 to 15 g / 10 min, depending on the configuration of the printed matter or laminated laminate (A) and the recycling method. When the melt mass flow rate (MFR) of the recycled plastic is within the above range, the occurrence of burns immediately after the start of extrusion and after continuous extrusion can be suppressed, and it is further suitable for various moldings. The manufacturing method of the present invention also preferably includes a step of adjusting the melt mass flow rate (MFR) of the recycled plastic by changing the thermal history. The measurement of the melt mass flow rate (MFR) of the recycled plastic is performed in the same manner as the measurement of the melt mass flow rate (MFR) of the printed matter described above.
[0148] (molded product) Molded products can be obtained by molding the recycled plastic obtained by the present invention. The molding method is not particularly limited, and examples include injection molding, extrusion molding, blow molding, and compression molding. Molded products can be used for various purposes such as home appliances, stationery, automobile parts, toys, sports goods, medical supplies, and building and construction materials.
[0149] (Film molding) The obtained recycled plastic can be, for example, heated and melted, extruded using a slit-shaped device called a T-die, molded into a film, and then cooled and solidified with a cooling roll to obtain a film molded product. The heat-melting temperature is preferably 100 to 210° C. The thickness of the film molded product is preferably 10 to 300 μm. EXAMPLES
[0150] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the present invention, parts and % represent parts by mass and % by mass unless otherwise noted.
[0151] (Hydroxyl value) The hydroxyl value is the number of milligrams of potassium hydroxide required to neutralize acetic acid bonded to hydroxyl groups when 1 g of a sample is acetylated, and was measured by the method described in JIS K 0070.
[0152] (Acid value) The acid value is the number of milligrams of potassium hydroxide required to neutralize the free fatty acids, resin acids, etc. contained in 1 g of a sample, and was measured by the method described in JIS K 0070.
[0153] (amine value) The amine value is the amount of potassium hydroxide in mg equivalent to the amount of hydrochloric acid required to neutralize the amino groups contained in 1 g of sample, and was measured in accordance with JISK 0070. That is, 0.5 to 2 g of sample was precisely weighed out (sample solid content: Sg). 50 mL of a mixed solution of methanol / methyl ethyl ketone = 60 / 40 (mass ratio) was added to the precisely weighed sample to dissolve it. Bromophenol blue was added to the obtained solution as an indicator, and the obtained solution was titrated with 0.2 mol / L ethanolic hydrochloric acid solution (titer: f). The point at which the color of the solution changed from green to yellow was set as the end point, and the titration amount (AmL) at this time was used to calculate the amine value according to the following formula. (Formula) Amine value = (A x f x 0.2 x 56.108) / S [mgKOH / g]
[0154] (mass average molecular weight) The weight average molecular weight was determined by measuring the molecular weight distribution using a gel permeation chromatography (GPC) device (HLC-8220 manufactured by Tosoh Corporation) and calculating the molecular weight converted using polystyrene as a standard substance. The measurement conditions are shown below. Columns: The following columns were used in series connection: Tosoh Corporation TSKgel Super AW2500 Tosoh Corporation TSKgel Super AW3000 Tosoh Corporation TSKgel Super AW4000 Tosoh Corporation's TSK gelguard column Super AWH Detector: RI (differential refractometer) Measurement conditions: Column temperature 40℃ Eluent: Tetrahydrofuran Flow rate: 1.0mL / min
[0155] (Glass transition temperature (Tg)) The glass transition point was determined by differential scanning calorimetry (DSC). The measurement was performed using a Rigaku Corporation DSC8231 under conditions of a measurement temperature range of -70 to 250°C and a heating rate of 10°C / min. The midpoint (inflection point) of the baseline shift based on the glass transition in the DSC curve was taken as the glass transition point.
[0156] (Chlorine content) The chlorine content was measured in accordance with JISK0127 (2013). That is, the ink or binder resin was applied to a transparent substrate to a thickness of 2.0 μm to form a coating film, dried at 80° C., and 0.5 g was scraped off. The scraped coating film was pretreated by a combustion method, and the chlorine content of the obtained sample was quantified by ion chromatography (LC-20ADsp, manufactured by Shimadzu Corporation) to determine the chlorine content. Regarding the printed matter or laminate (A), the chlorine content was determined in the same manner as above, except that 0.5 g of the test object was cut out and pretreated by the combustion method and used as the sample.
[0157] (Melt Mass Flow Rate (MFR) Measurement) The MFR was measured at a temperature of 190° C. and a pressure of 2.6 kgf according to the method described in JIS K 7210-1: 2014. The MFR of the printed matter or laminate (A) was measured after crushing it into pieces with side lengths of 5 mm to 10 mm.
[0158] (Calculation of polyolefin resin content) The content of the polyolefin resin in the printed matter or laminate (A) was calculated using the following formula. Formula: (mass of polyolefin resin in printed matter or laminate (A)) / (mass of printed matter or laminate (A))×100
[0159] <Synthesis of urethane resin> (Synthesis Example 1) Urethane resin PU1 23.6 parts of polyester polyol PE1 (biomass content 60%) having a number average molecular weight of 2,000, which is a condensation product of diol (neopentyl glycol (NPG) / 1,3-propanediol (1,3-PD=50 / 50) and dibasic acid (adipic acid / sebacic acid=50 / 50), 4.7 parts of isophorone diisocyanate (IPDI), 7.5 parts of ethyl acetate, and 7.5 parts of propyl acetate were mixed and reacted at 90°C for 5 hours in a nitrogen atmosphere to obtain a urethane prepolymer with a terminal isocyanate. Next, 1.6 parts of isophoronediamine (IPDA), 0.1 parts of dibutylamine (DBA) and 55 parts of mixed solvent 1 (ethyl acetate / isopropanol=60 / 40 (mass ratio)) were mixed with stirring, and the obtained urethane prepolymer with terminal isocyanate was gradually added at 40°C. The mixture was reacted at 80° C. for 1 hour to obtain a solution of urethane resin PU1 having a solid content of 30% by mass, an amine value of 4 mg KOH / g, and a mass average molecular weight of 70,000. The chlorine content of urethane resin PU1 was 0% by mass.
[0160] <Synthesis of urethane resin> (Synthesis Examples 2-4) Urethane Resins PU2-4 Urethane resins PU2 to PU4 were obtained in the same manner as in Synthesis Example 1, except that the dibasic acid was changed to the raw material described below. PU2: Dibasic acid (adipic acid / succinic acid=50 / 50) Solid content 30% by mass, amine value 4.2 mgKOH / g, mass average molecular weight 68,000 Biomass content in urethane resin: 48% PU3: Dibasic acid (adipic acid / dimer acid=50 / 50) Solid content 30% by mass, amine value 3.9 mgKOH / g, mass average molecular weight 72,000 Biomass content in urethane resin: 48% PU4: Dibasic acid (adipic acid = 100) Solid content 30% by mass, amine value 4.1 mgKOH / g, mass average molecular weight 69,000 Biomass content in urethane resin: 29%
[0161] Details of the raw materials used in the following ink preparation examples are as follows: Rosin resin solution: A 30% solids solution of rosin ester (acid value 10 mg KOH / g, mass average molecular weight 500-1500, softening point 87°C), an ester condensate of rosin acid and glycerin, in ethyl acetate. Cellulose acetate propionate (CAP) resin solution: Cellulose acetate propionate resin (CAP-504-0.2 manufactured by Eastman Chemical Co., glass transition point 160°C, mass average molecular weight 40,000, chlorine content 0% by mass, nitrification degree 0% by mass) in ethyl acetate with a solid content of 30% Nitrocellulose (NC) resin solution: DLX5-8: ICI Novel Enterprises Nitrocellulose (nitrogen content 12.0%) solids 30% isopropanol solution Polyvinyl butyral (PVB) resin solution: A 30% solids solution of polyvinyl butyral resin (glass transition point 70°C, mass average molecular weight 50,000, chlorine content 0% by mass) having vinyl alcohol units, vinyl acetate units, and vinyl butyral units and containing 73% by mass of butyral ring groups, in a mixed solvent of ethyl acetate:isopropanol = 50:50 (mass ratio). Polyamide resin solution: A 30% solids solution of polyamide resin (amine value 3.5 mgKOH / g, softening point 116°C, mass average molecular weight 6,000) containing 50% or more by mass of structural units derived from dimer acids made from oleic acid and linoleic acid. Vinyl chloride-vinyl acetate resin solution: Vinyl chloride-vinyl acetate copolymer resin (Nissin Chemical Solvine TA3, chlorine content 47.1% by mass) 30% solids solution in ethyl acetate Chlorinated polypropylene solution: Chlorinated polypropylene resin (803M made by Nippon Paper Industries, chlorine content 30%)
[0162] <Ink preparation> (Gravure ink preparation example 1) Gravure ink X1 40 parts of urethane resin PU1 solution, 15 parts of CAP resin solution, 5 parts of CI pigment blue 15:3 (manufactured by Toyo Color Co., Ltd., product name: LIONOLBLUE FG-7330, chlorine content 0% by mass, nitrification degree 0% by mass), silica particles (hydrophilic silica, average particle diameter 3.0 μm, specific surface area 300 m 2 A pigment dispersion was obtained by mixing 0.8 parts of chlorinated polypropylene solution, 3.5 parts of propylene glycol monomethyl ether (boiling point 121.0°C), and 1.5 parts of water with a bead mill, and the resulting pigment dispersion was mixed with stirring to obtain an organic solvent-based gravure ink X1.
[0163] (Gravure ink preparation examples 2-8, Comparative preparation examples 1-2) Gravure inks X2-8, Y1-2 Gravure inks X2 to 8 and Y1 to 2 were obtained in the same manner as in Gravure Ink Preparation Example 1, except that the raw materials and charging ratios were changed to those shown in Table 1.
[0164] [Table 1]
[0165] <Preparation of adhesive> (Synthesis Example 5) Urethane resin PU5 77 parts of polyester polyol PE5 (biomass content 100%) having a number average molecular weight of 2,000, which is a condensation product of 1,3-propanediol (1,3-PD) and dibasic acid (sebacic acid / succinic acid = 70 / 30), 1.5 parts of trimethylolpropane (TMP) and 7.3 parts of ethyl acetate were mixed and heated at 50 ° C for 30 minutes to obtain a urethane prepolymer with terminal isocyanate. Next, 6.8 parts of tolylene diisocyanate and 7.3 parts of ethyl acetate were stirred and mixed, and the obtained urethane prepolymer with terminal isocyanate was gradually added and reacted at 70 ° C for 1.5 hours. Then, 0.101 parts of titanium tetrabutoxide was added, the temperature was raised to 90 ° C, and the reaction was allowed to proceed for 5 hours. The reaction solution was diluted with ethyl acetate to obtain a solution of urethane resin PU5 with a solid content of 70% and a mass average molecular weight of 23,000.
[0166] (Adhesive Preparation Example 1) Biomass Adhesive Z1 A solution of 31.6 parts by mass of urethane resin PU5 (solid content 70%), 10.5 parts by mass of hardener Takenate A5 (MDI / TMP, solid content 80%, manufactured by Mitsui Chemicals SKC Polyurethanes), and 57.9 parts by mass of ethyl acetate were mixed and stirred to prepare biomass adhesive Z1 with a biomass content of 72%.
[0167] <Preparation of Barrier Coating Agent> Barrier Coating Agent C1 8 parts of polyvinyl alcohol with a degree of saponification of 98 mol % and a 4% aqueous solution viscosity of 30 mPa·s, 2 parts of montmorillonite, and 90 parts of water were mixed and dissolved by heating and stirring at 90°C to obtain barrier coating agent C1.
[0168] <Production of printed matter or laminate (A)> The printed matter or laminate (A) was produced by the following method. The MFR, olefin content, chlorine content, and biomass degree of each are shown in Table 2.
[0169] (Production Example 1) Laminate A1 The gravure ink X1 was diluted with a mixed solvent of ethyl acetate / isopropyl alcohol (mass ratio 70 / 30) so that the viscosity was 15 seconds (25°C) using Zahn cup #3 (manufactured by Rigo Co., Ltd.). Then, a corona-treated biaxially oriented polypropylene (OPP) film (thickness 20 μm) was printed using a gravure printing machine equipped with a gravure plate with a plate depth of 35 μm, and dried at 50°C to obtain a printed matter having a configuration of OPP / printed layer. Next, using a dry laminating machine, adhesive Z2 ("TM-340V / CAT-29B" manufactured by Toyo Morton Co., Ltd.) was applied onto the printed layer, and after drying the solvent in an oven, a non-oriented polypropylene (CPP) film (thickness 30 μm) was laminated onto the adhesive layer at a line speed of 40 m / min, and the mixture was kept warm at 40°C for one day to obtain a laminate A1 having a configuration of OPP / printed layer / adhesive layer / CPP. The coating amount of the printed layer and the adhesive layer after drying was 2.5 g / m2, respectively. 2 It was decided.
[0170] (Manufacturing examples 2-7) Laminate A2-7 Laminates A2 to A7 having a structure of OPP / printed layer / adhesive layer / CPP were obtained in the same manner as in the production process of laminate A1, except that gravure ink X1 was changed to gravure inks X2 to X7. The coating amount after drying of the printed layer and the adhesive layer was 2.5 g / m2, respectively. 2 It was decided.
[0171] (Manufacturing example 8) Printed matter A8 Gravure ink X7 was diluted with an ethyl acetate / isopropyl alcohol mixed solvent (mass ratio 70 / 30) so that the viscosity was 15 seconds (25°C) using Zahn cup #3 (manufactured by Rigo Co., Ltd.). It was then printed on a corona-treated biaxially oriented polypropylene (OPP) film (thickness 20 μm) using a gravure printing machine equipped with a gravure plate with a plate depth of 35 μm, and dried at 50°C to obtain a printed matter having a configuration of OPP / printing layer. The coating amount of the printing layer after drying was 2.5 g / m 2 It was decided.
[0172] (Manufacturing example 9) Printed matter A9 A printed matter A9 having a structure of OPP / printed layer was obtained in the same manner as in the production process of laminate A8, except that gravure ink X7 was changed to gravure ink X8.
[0173] (Production Example 10) Printed matter A10 A printed matter A10 having a structure of HDPE / printed layer was obtained in the same manner as in the production process of laminate A8, except that the substrate was changed to a high density polyethylene (HDPE) film (thickness 20 μm).
[0174] (Manufacturing example 11) Printed matter A11 A printed matter A11 having a structure of HDPE / printed layer was obtained in the same manner as in the production process of laminate A9, except that the substrate was changed to a high density polyethylene (HDPE) film (thickness 20 μm).
[0175] (Production Example 12) Laminate A12 A laminate A12 having a structure of HDPE / printed layer / adhesive layer / LLDPE was obtained in the same manner as the laminate A1, except that the substrate was changed to a high density polyethylene (HDPE) film (thickness 20 μm) and the sealant was changed to a linear low density polyethylene (LLDPE) film (thickness 40 μm). The coating amount of the printed layer and the adhesive layer after drying was 2.5 g / m2 each. 2 It was decided.
[0176] (Production Example 13) Laminate A13 Barrier coating agent C1 was applied to a corona-treated biaxially oriented polypropylene (OPP) film (thickness 20 μm) using a gravure printing machine equipped with a gravure plate, and the solvent was dried in an oven to obtain an intermediate laminate having an OPP / barrier coating layer structure. Thereafter, a laminate A13 having a structure of OPP / barrier coat layer / printed layer / adhesive layer / CPP was obtained in the same manner as in the production process of the laminate A1. The coating amount of the printed layer and the adhesive layer after drying was 2.5 g / m2 each. 2 The coating amount of the barrier coat layer after drying was 2.0 g / m 2 It was decided.
[0177] (Production Example 14) Laminate A14 A laminate A20 having an OPP / printed layer / barrier adhesive layer / CPP structure was obtained in the same manner as the laminate A1, except that the adhesive was changed to Barrier Adhesive Z3 ("TM-9310 / CAT-1980" manufactured by Toyo-Morton Co., Ltd.). The coating amount of the printed layer and the barrier adhesive layer after drying was 2.5 g / m2 each. 2 It was decided.
[0178] (Production Example 15) Laminate A15 The sealant is applied to aluminized non-oriented polypropylene (VMCPP) film (thickness 3 Except for changing the thickness of the laminate to 0 μm, the manufacturing process was the same as that of the laminate A1, with the exception that the thickness of the laminate was changed to OPP / printing layer / adhesive. A laminate A3 having a printing layer / VMCPP structure was obtained. The coating amount of the printing layer and the adhesive layer after drying was 2.5 g / m 2 It was decided.
[0179] (Production Examples 16 and 17) Laminates A16 and A17 Except for changing the gravure ink X1 to gravure ink Y1 or Y2, the same manufacturing process as for the laminate A1 was used to obtain laminates A16 and A17 having a structure of OPP / printing layer / adhesive layer / CPP. The coating amount of the printing layer and the adhesive layer after drying was 2.5 g / m, respectively. 2 It was decided.
[0180] (Production Example 18) Laminate A18 A laminate A18 having a structure of NY / printed layer / adhesive layer / CPP was obtained in the same manner as in the production process of the laminate A1, except that the substrate was changed to a nylon (NY) film (thickness 15 μm). The coating amount after drying of the printed layer and the adhesive layer was 2.5 g / m, respectively. 2 It was decided.
[0181] (Production of Laminate (A) 19) Laminate A19 A laminate 19 having an OPP / printed layer / adhesive layer / CPP structure was obtained in the same manner as the manufacturing process of the laminate A1, except that the adhesive was changed to Z1. The coating amount of the printed layer and the adhesive layer after drying was 2.5 g / m, respectively. 2 It was decided.
[0182] (Production of Laminate (A) 20) Laminate A20 A laminate 20 having a structure of HDPE / printed layer / adhesive layer / LLDPE was obtained in the same manner as the manufacturing process of the laminate A12, except that the adhesive was changed to Z1. The coating amount of the printed layer and the adhesive layer after drying was 2.5 g / m, respectively. 2 It was decided.
[0183] <Production of recycled plastic (B)> (Example 1) Recycled plastics B1 and BB1 The laminate A1 (100 kg) was crushed into pieces of 2 cm x 2 cm using a cutter mill (U-210, manufactured by Nishimura Machinery Works), washed with water, dehydrated using a centrifugal dehydrator (YDK-FS type, manufactured by Iwatsuki Machinery Works), and further dried with hot air until the moisture content reached 0.5%. The laminate A1 obtained through the above steps, Irganox 1010 (phenolic antioxidant), and UMEX 1010 (maleic anhydride modified polypropylene compatibilizer) were fed into a twin-screw extruder (manufactured by Japan Steel Works, Ltd., screw diameter: 34 mm, minimum gap distance between the cylinder inner wall and the screw: 0.4 mm) and melted and kneaded for 30 seconds at a screw rotation speed of 200 rpm, 230°C, and an extrusion flow rate of 20 kg / h. The amount of Irganox 1010 added to the laminate A1 was adjusted to 0.2% by mass relative to 100% by mass of the laminate A1. The amount of Eumex 1010 added to the laminate A1 was adjusted to 0.15% by mass relative to 100% by mass of the laminate A1.
[0184] Then, the mixture was extruded from the discharge part of the extrusion device using a 120 mesh screen. The pressure of the discharge part immediately after the start of extrusion was 2 MPa. The extruded resin composition was immediately cut with a pelletizer and cooled by immersing in cold water. In this way, recycled plastic B1 in the form of pellets was obtained, which was recycled from the laminate A1. After obtaining the recycled plastic B1, the operation was continued for 5 hours (long run) under the manufacturing conditions of the recycled plastic B1, and the extruded resin composition after 5 hours was immediately cut with a pelletizer and cooled by immersing it in cold water. The pressure at the discharge part after 5 hours of continuous extrusion was 4 MPa. In this way, the recycled plastic BB1 in the form of pellets, which was recycled in a long run from the printed matter A1, was obtained.
[0185] (Examples 2 to 25, Comparative Examples 1 to 5) Recycled plastics B2 to B30, BB2 to 30 For the above printed matter or laminates A1 to A18, B2 to B30 and BB2 to BB30 were obtained in the same manner as in Example 1 (the manufacturing process of recycled plastics B1 and BB1) using the raw materials and conditions shown in Table 2. Note that in Example 24, no antioxidant was added, and in Example 25, no compatibilizer was added.
[0186] (Examples 26 to 31) Recycled plastics B31 to B36, BB31 to 36 B31 to B36 and BB31 to BB36 were obtained, respectively, in the same manner as in Example 1 (the manufacturing process for recycled plastics B1 and BB1), except that the antioxidant or compatibilizer was changed as described below. Example 26 Antioxidant: Irgafos168: phosphoric acid-based antioxidant (manufactured by BASF) Example 27 Antioxidant: Irganox PS 800FL: Sulfur-based antioxidant (manufactured by BASF) Example 28 Antioxidant: Nolac CD: Amine-based antioxidant (manufactured by Ouchi Shinko Chemical Industry Co., Ltd.) Example 29 Compatibilizer: Bondfast E: ethylene-glycidyl methacrylate copolymer-based compatibilizer (manufactured by Sumitomo Chemical Co., Ltd., melting point: 103°C) Example 30 Compatibilizer: Bondfast-7L: ethylene-glycidyl methacrylate copolymer-based compatibilizer (manufactured by Sumitomo Chemical Co., Ltd., melting point: 60°C) Example 31 Compatibilizer: Bondfast-7M: ethylene-glycidyl methacrylate copolymer-based compatibilizer (manufactured by Sumitomo Chemical Co., Ltd., melting point: 52°C)
[0187] (Example 32) Recycled plastics B37 and BB37 B37 and BB37 were obtained in the same manner as in Example 1 (the manufacturing process for recycled plastics B1 and BB1), except that the laminate was changed to A19.
[0188] (Example 33) Recycled plastics B38 and BB38 B37 and BB37 were obtained in the same manner as in Example 19 (production process of recycled plastics B19 and BB19), except that the laminate was changed to A20.
[0189] <Evaluation of recycled plastics> The pellet-shaped recycled plastics obtained in the above Examples and Comparative Examples were extrusion-molded at 230° C. using a T-die extruder to produce a film-shaped molded product having a thickness of 50 μm. The following evaluations were performed using the film-shaped molded product.
[0190] (Foreign matter evaluation) The obtained film-like molded product was cut into 0.5 m 2 The number of foreign particles (approximately 100 μm or larger) that could be visually identified per unit area was counted and evaluated according to the following criteria, where A, B, and C are ranges that are acceptable for practical use. A (Good): The number of foreign objects is less than 50. B (Acceptable): The number of foreign objects is between 50 and 100. C (Acceptable): The number of foreign objects is between 100 and 200. D (defective): 200 or more foreign objects
[0191] (Burst rating) The film-like molded product thus obtained was evaluated for visually discernible fading according to the following criteria, where A, B, and C are within the range of acceptable practical use. A (Good): No marks (no color change) B (Fair): Slightly scorched (some areas have turned light brown) C (Fair): Burns are visible (light brown discoloration is visible in multiple areas or overall) D (Poor): Many burns are observed (black or brown foreign objects or discolored areas are observed)
[0192] (Evaluation of moldability: bottle foaming property) The pellets of the recycled plastic (B) were blow molded at 220°C using a blow molding machine to produce bottle-shaped molded bodies with a thickness of 1 mm. For each bottle, the number of bottles that showed visible bubbles was counted per 50 bottles. A (Good): Effervescence was observed in 1 or less of 50 bottles. B (Acceptable): 2 to 3 bottles out of 50 showed bubbles. C (Acceptable): 4 to 5 bottles out of 50 showed bubbles. D (Defective): 6 or more bottles out of 50 had bubbles.
[0193] (Evaluation Results) The evaluation results of Examples 1 to 25 and Comparative Examples 1 to 5 are shown in Table 2. As with the evaluation result of Example 1, the evaluation results of Examples 26 to 33 were all rated A in all items.
[0194] [Table 2]
[0195] From the above results, in Comparative Examples 1 and 2, the discharge pressure from the discharge part of the extrusion device exceeded 18 MPa, so the burn evaluation after continuous extrusion was poor. In Comparative Examples 3 and 4, the chlorine content in the laminate (A) exceeded 0.4 mass% of the total mass of the laminate (A), so the moldability was poor. In Comparative Example 5, the olefin content in the laminate was less than 80 mass% of the total mass of the laminate, so the foreign matter evaluation immediately after the start of extrusion and after continuous extrusion was poor. In the examples, the printed matter or laminated laminate (A) includes a substrate and a printed layer, the chlorine content of the printed matter is 0.4 mass% or less based on the total mass of the printed matter or laminated laminate (A), the printed matter contains 80 mass% or more of polyolefin resin based on the total mass of the printed matter or laminated laminate (A), the printed matter or laminated laminate (A) contains a biomass-derived resin, the biomass-derived resin contains at least one resin selected from the group consisting of urethane resin, rosin resin, and cellulose resin, and the pressure from the discharge part of the extrusion device is 18 MPa or less, so that a recycled plastic having excellent moldability and little foreign matter and discoloration immediately after the start of extrusion and after continuous extrusion could be obtained.
Claims
1. A method for producing recycled plastic, comprising the steps of: obtaining recycled plastic (B) from a printed matter or laminate (A) using an extrusion device equipped with a first screw and a discharge section, The printed matter and the laminate (A) have not been subjected to a process of removing the printed layer from the substrate, The printed matter or laminate (A) comprises a substrate and a printed layer, and The printed matter or laminate (A) contains a polyolefin resin in an amount of 80 mass% or more based on the total mass of the printed matter or laminate (A), The chlorine content of the printed matter or laminate (A) is 0.4 mass% or less based on the total mass of the printed matter or laminate (A), The printed matter or laminate (A) contains a biomass-derived resin, The biomass-derived resin is At least one resin selected from the group consisting of a urethane resin, a rosin resin, and a cellulose resin, a heating, melting and kneading step of heating, melting and kneading the printed matter or laminate (A) in the extrusion device to obtain a resin composition (a); and A method for producing recycled plastic, comprising an extrusion step in which the resin composition (a) is extruded from a discharge portion of an extrusion device at a pressure of 18 MPa or less.
2. The method for producing recycled plastic according to claim 1, wherein the heat melting temperature is 120 to 280°C.
3. The method for producing recycled plastic according to claim 1 or 2, wherein the biomass content of the printed matter or laminate (A) is 0.5% or more.
4. The method for producing recycled plastic according to claim 1 or 2, wherein the urethane resin contains structural units derived from polyester, which is a condensation product of a dibasic acid and a diol, and the dibasic acid contains at least one selected from the group consisting of sebacic acid, succinic acid, and dimer acid.
5. The method for producing recycled plastics according to claim 1 or 2, wherein the printed matter or laminate (A) further contains a polyvinyl acetal resin.
6. The method for producing recycled plastics according to claim 1 or 2, wherein the polyolefin resin comprises a polyethylene resin and / or a polypropylene resin.
7. The method for producing recycled plastic according to claim 1 or 2, wherein the printed matter or laminate (A) further comprises a barrier layer.
8. The method for producing recycled plastic according to claim 7, wherein the barrier layer is at least one selected from the group consisting of a vapor deposition layer including a vapor deposition film, a barrier coat layer, and a barrier adhesive layer.
9. The method for producing recycled plastic according to claim 1 or 2, further comprising a water cooling step.
10. The method for producing recycled plastic according to claim 1 or 2, wherein the melt mass flow rate of the printed matter or laminate (A) is 0.5 to 15 g / 10 min.
11. The method for producing recycled plastic according to claim 1 or 2, wherein the printed layer contains a binder resin, and the chlorine content of the binder resin is 5% by mass or less.
12. The method for producing recycled plastic according to claim 1 or 2, wherein the rotation speed of the first screw of the extrusion device is 50 to 1000 rpm.
13. The method for producing recycled plastic according to claim 1 or 2, wherein the printed matter or laminate (A) further comprises an adhesive layer, and the adhesive layer comprises a cured product of a polyisocyanate and a polyol.
14. The method for producing recycled plastics according to claim 1 or 2, wherein the heating, melting and kneading step is carried out in the presence of an antioxidant.
15. The method for producing recycled plastic according to claim 1 or 2, wherein the heating, melting and kneading step is carried out in the presence of a compatibilizer.
16. A method for producing a molded product of recycled plastic, produced by the method for producing recycled plastic according to claim 1 or 2.
Citation Information
Patent Citations
Ink remover for recycling plastic laminate into recycled materials, ink film separation / removal method, and method of isolating and recovering separated or removed ink film
WO2021230032A1
